Long-term fertilization enhances Bacilli cell size by increasing soil resource availability and shifting its metabolic strategies - Nan Rong; Youzhi Feng; Ruirui Chen; Yuanyuan Bao; Shiying He; Shudong Ding; Xiaoyuan Yan (Agriculture, Ecosystems & Environment, 2026)

First report of Fusarium weifangense, F. puerense and F. asiaticum causing leaf spot disease on Morus alba L. in China - Mei Lei; Rong Xiao; Lixia Zhang; Yu Tian; Zhongrong Zheng; Zehui Zhao; Tingting Zhao; Zhu Li; Haixia Ding (Crop Protection, 2026)

Deep-water carbonate chemistry and CaCO3 burial in the North Indian Ocean since the last glaciation - Jie Tian; Rong Xiang; Sui Wan; Yi Zhong; Fuchang Zhong; Yiping Yang; Wubiao Li; Liyuan Wu; Ping Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Polyhydroxybutyrate production-oriented wastewater valorization: Aniline as a selective stress enabling non-sterile operation - Chunyu Du; Ziqian Wang; Rong Li; Guanyu Zheng; Dahu Ding (Water Research, 2026)

DNA methylome analysis reveals EjABCG23-mediated epigenetic regulation underlying fruit russeting in white-fleshed loquat - Kun Zhang; Yuying Ding; Rong Su; Chang Liu; Xuelian Li; Yang Wang; Yan Deng; Qiong Zhou; Xiaojun Chen; Yuxing Li; Qunxian Deng (Postharvest Biology and Technology, 2026)

Synergistic organic–inorganic hybrid interlayer enables tunable Zn2+ desolvation and nucleation toward dendrite-free zinc metal anodes - Xiangzhong Kong; Zicong Wang; Weijia Lv; Yuyang Ding; Xi Chen; Zhongmin Wan; Shi Li; Liya Rong (Chemical Engineering Journal, 2026)

Viper-inspired vigilance: A biomimetic PPy@M(OH)(OCH3) (M = Co, Ni) smart armor endows cotton with high-efficient fire-resistance, graded fire-alarming, and identification for firefighting postures - Caiyu Rong; Xiang Dong; Shidai Zhang; Shuqin Ding; Zhaoxin Zhang; Yan Ma; Zixin Lin; Yuhe Song; Jiayi Zhang; Shibin Nie; Konghu Tian (Chemical Engineering Journal, 2026)

A robot herding strategy combining CMFF and MPC for shepherding - Hongbo Liu; Ping Song; Gang Liu; Xiaoping Xin; Yuping Rong; Luyu Ding; Junyao Gao; Zhuoming Wang; Yinglong Zhang; Pengzhen Li (Computers and Electronics in Agriculture, 2026)

Flexural behavior of coarse aggregate-UHPC bridge slabs: A combined phase analysis and layered strength model approach - Qizhi Xu; Shimin Ding; Yan Tang; Jingquan Wang; Hui Rong; Yiming Yao (Engineering Structures, 2026)

Aerosol-induced dimming and deposition limit solar PV potential in China: regional heterogeneity and clean-air co-benefits - Kexin Wang; Rong Tang; Haotian Zheng; Fabian Wagner; Derong Zhou; Aijun Ding; Haikun Wang (Atmospheric Environment, 2026)

Retraction notice to “Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study” [Sci. Total Environ. 883 (2023) 163662] - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2026)

Biodegradable plastic mulches: Distinct effects on microbial communities but no impact on soil multifunctionality during cabbage production - Rong Liang; Lei Mei; Jina Ding; Li Wang; Mouliang Xiao; Yongfu Li; Xiao Liu; Changlong Shao; David R. Chadwick; Davey Jones; Fan Ding; Can Hu; et al. (Journal of Hazardous Materials, 2026)

China could simultaneously increase wheat yield and nitrogen use efficiency under the temperature rise of 1 ℃ through optimal crop managements - Kaiyuan Gong; Shuoqiu Ding; Yadong Luo; Yinghua Zhang; Xiao Wang; Fengying Duan; Xia Li; Liangbing Rong; Zhihao He; Hao Feng; Qiang Yu; Wenbin Zhou; et al. (European Journal of Agronomy, 2026)

Biochar–bentonite composite enabling antibiotic removal and greenhouse gas mitigation in waters - Yan Sun; Xiang Jia; Le Dai; Wei Ding; Yongjie Wang; Jin Zhang; Huan He; Nan Rong; Pei Lei (Chemical Engineering Journal, 2026)

Correction to: The Cerebrovascular Reactivity Adjusted Fractional Amplitude of Low-Frequency Fluctuations Abnormalities in Middle Cerebral Artery Stenosis and Occlusive Disease - Liqing Zhang; Luoyu Wang; Xue Tang; Yidi Zhu; Rong Wang; Zhongxiang Ding (Translational Stroke Research, 2026)

Whole-transcriptome profiling reveals the landscape of host circular RNAs during grass carp reovirus infection - Tian Bu; Dongmei Zhong; Fang Gou; Yinggang Li; Siwan Xu; Yifei Wang; Jinwang Ding; Rong Yang; Shaojun Liu (Aquaculture, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Corrigendum to “Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide” [Food Res. Int. 230 (2026) 118574] - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying Li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Remediation effects of humic acid and hydroxyapatite on cadmium-contaminated alkaline wheat soil and its microbial community response: A field trial - Yineng Lu; Haoyu Yue; Rong Tan; Zihao Ding; Geng Chen; Shuangting Zhang; Ziyi Li; Ram Proshad; Xiuwen Cheng; Zhuanjun Zhao (Journal of Environmental Sciences, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Depth-coupling pattern between forest soil microorganisms and carbon mineralization in southwestern China - Shuang Ding; Shengzhao Wei; Honghong Lin; Li Rong; Enwei Zhang; Xue Yang; Huanxu Lv; Xingwu Duan (CATENA, 2026)

Imbalanced Si:N Alters Lipid Production and Photosynthesis in the Marine Diatom Phaeodactylum tricornutum and Dinoflagellate Prorocentrum donghaiense - Jiaxuan Cui; Chuanli Zhang; Rong Bi; Yunyun Zhuang; Xiaoqian Pan; Xiao Qin; Zhong Cao; Hailong Zhang; Li Li; Yang Ding; Meixun Zhao (Journal of Ocean University of China, 2026)

Formation, Potential, and Challenges of Marine-Continental Transitional Shale Gas in China - Caineng Zou; Dazhong Dong; Qin Zhang; Weiliang Kong; Wen Liu; Zhenyu Zhao; Zhi Yang; Qun Zhao; Rong Ding; Guangyin Cai; Tianquan Qu; Wanli Gao; et al. (Journal of Earth Science, 2026)

Eliminating high-voltage phase transitions and oxygen loss in O3-type sodium layered cathodes via reversible solid-solution and anionic-redox chemistry - Lin-Rong Wu; Yu-Han Zhang; Zhen Wu; Hui Wu; Nian Zhang; Ding Zhang; Xiaochuan Duan; Xian-Ming Zhang (Science Bulletin, 2026)

Guaianolide sesquiterpenoids from Chrysanthemum indicum L. alleviate rheumatoid arthritis by targeting of NLRP3 inflammasome pathway - Gui-Min Xue; Hao Feng; Dong-Rong Zhu; Xin-Xin Guo; Ding-Qiao Xu; Yan-Jun Sun; Yan-Le Zhi; Zhi-Qiang Zhang; Guo-Sheng Li; Fa-Wu Dong; Jin-Feng Xue (Phytochemistry, 2026)

Valorization of catalytically improved combustion stability for low-concentration methane in a gradient pore-density porous media burner - Yunqi Cao; Haonan Rong; Li Yang; Yifan Ding; Fang Liu; Cheng Zhai (Fuel, 2026)

Non-volumetric phase transition of PNIPAM enables high-sensitivity temperature monitoring and photoelectric therapy for wound care - Jie Ding; Danni Hou; Yuan Tian; Rong Li; Yuyan Wang; Junzhong Jiang; Yucai Hu; Chengheng Wu; Dan Wei; Jing Sun; Zi Qiao; Hongsong Fan (Chemical Engineering Journal, 2026)

SAA-YOLO: A scale-aware attention enhanced YOLOv10 for UAV-based detection of medicinal plant Phlomoides rotata in alpine grasslands - Rong Ding; Chenghui Wang; Xuemei Wu; Guopeng Chen; Jiangkai Yang; Hongmei Jia; Shihong Zhong; Rui Gu (Computers and Electronics in Agriculture, 2026)

Erosion obliges fungi to maintain community diversity through stochastic processes - Shuang DING; Shengzhao WEI; Li RONG; Xingwu DUAN (Pedosphere, 2026)

The transcription factor SlPLATZ22 negatively regulates salinity tolerance in tomato plants - Xin Li; Fei Ding; Niannian Zhou; Zheng Chen; Jiahui Huang; Fangling Jiang; Carl-Otto Ottosen; Ron Mittler; Rong Zhou; Zhen Wu (Journal of Plant Physiology, 2026)

Boron fortifies a dual barrier in rice roots: How Casparian strip reinforcement and cell wall remodeling restrict cadmium entry - Zhihong Guo; Min Nie; Ting Li; Changfeng Ding; Gaoxiang Huang; Zhengfu Yue; Yurong Wang; Taolin Zhang; Rong Huang; Xingxiang Wang (Journal of Hazardous Materials, 2026)

Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Ultrasound-assisted dry-heating glycosylation with xylooligosaccharides: Enhancing the structural and functional properties of pig skin collagen - Shengqi Jiang; Lin Li; Hongqing Nie; Jincheng Han; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Huiyu Han; Jing Xi; Wu Ding (Food Hydrocolloids, 2026)

The Cerebrovascular Reactivity Adjusted Fractional Amplitude of Low-Frequency Fluctuations Abnormalities in Middle Cerebral Artery Stenosis and Occlusive Disease - Liqing Zhang; Luoyu Wang; Xue Tang; Yidi Zhu; Rong Wang; Zhongxiang Ding (Translational Stroke Research, 2026)
This study investigated the variation characteristics of static fractional amplitude of low-frequency fluctuations (sfALFF) and dynamic fALFF (dfALFF) in Middle cerebral artery stenosis or occlusion(MCA-S) patients, and explored these two indicators alterations with cerebrovascular reactivity (CVR) correction. A total of 41 MCA-S patients and 50 matched controls underwent resting-state functional MRI and neuropsychological testing. Group differences in sfALFF/dfALFF were compared between the two groups, and the brain regions with differences in sfALFF/dfALFF with and without CVR correction were explored. Subsequently, partial correlation analysis was employed to evaluate the correlation between the abnormal brain regions and neuropsychological assessments. After CVR correction, MCA-S patients displayed increased sfALFF in Vermis_6, ipsilesional Cerebelum_8, Hippocampus, and other regions, alongside elevated dfALFF in Vermis_7, ipsilesional Hippocampus, and contralesional Cerebelum_8 ( P < 0.001). No significant correlations were found between fALFF metrics and neuropsychological scores post-Bonferroni correction. Uncorrected analyses showed group differences in sfALFF/CVR within ipsilesional Occipital_Mid and Parietal_Inf, while CVR-adjusted results revealed changes in ipsilesional Cerebelum_8 and contralesional Caudate ( P < 0.05). For dfALFF, uncorrected differences emerged in ipsilesional Postcentral, whereas CVR correction highlighted ipsilesional Temporal_Inf alterations. In summary, MCA-S patients exhibited abnormal neuronal activity associated with both sfALFF and dfALFF. With CVR correction, vascular confounding effects on the BOLD signal were partially mitigated, thereby enabling more accurate reflection of underlying neural activity alterations.

Influence of sample purity on landslide susceptibility mapping: a mutually exclusive stratified purity strategy based on the state-process consistency - Jiaying Zhu; Yuqian Yang; Shuangyun Peng; Zhiqiang Lin; Ziyi Zhu; Xianchun Pan; Xue Ding; Rong Jin (Bulletin of Engineering Geology and the Environment, 2026)
The quality and uncertainty of training samples are a critical bottleneck constraining the performance of machine learning in landslide susceptibility mapping (LSM). To address this, this study introduces a sample purity optimization framework based on state-process consistency (SPC). The framework utilizes two indices, SWCFD and CF-BE-HMD, combined with a mutually exclusive stratified purity strategy (MESPS), to systematically optimize the purity of the training samples. The framework was validated using data from Zhenxiong County, Yunnan Province, China. The results indicate that sample purity is the core variable influencing LSM model performance. The mutually exclusive sample group with the highest purity achieved AUC values of 0.92–0.93, markedly higher than those of other groups. High-purity landslide and non-landslide samples effectively suppressed the risk generalization effect caused by low-purity positive samples and overcame the risk conservatism problem induced by low-purity negative samples, resulting in clearer boundaries in the risk zonation. Therefore, only through bidirectional purification, which ensures that both positive and negative samples are highly representative, can these two extreme biases be maximally eliminated, leading to the generation of scientific, reliable, and balanced landslide susceptibility maps. This study offers a feasible solution to the sample quality bottleneck, providing a solid theoretical and empirical basis for shifting landslide modeling towards a quality-driven approach.

Metallogenic Age of the Qianjiadian Uranium Deposit—Evidence from Fluid Inclusions and (U-Th)/He - Ruxin Ding; Yangshijia Li; Zilong Li; Rongli Huang; Minqiang Cao; Xingzhou Chen; Hui Rong; Heping Zou (Journal of Earth Science, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

A scalable human liver-on-a-chip platform for predictive safety assessment - Gauri Kulkarni; Lizao Chen; Jing Sang; Ji Hye Seo; Romain Grall; Yunfang Wang; Paige Gilbride; Yu-Chieh Yuan; Matthew Albaum-Getzen; Jenna McCormack; Jingzhe Ma; Alyssa Fanelli; et al. (Toxicology, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Mechanism study on ultrasonication combined with soybean 11S globulin to improve the quality and flavor compounds of low-salt lamb meat gel - Rong Bai; Hongqing Nie; Jing Xi; Aitmagambetova Madina; Lin Li; Huiyu Han; Shengqi Jiang; Gege Wang; Wu Ding (Meat Science, 2026)

Post-imprinting modification of molecularly imprinted polymers for ultrasensitive screening chloramphenicol type antibiotics and risk assessment in urban environmental water - Sitao Wang; Yi Yang; Xiaoqing Shi; Rong Fan; Yujie Ding; Juan Wu; Zhigang Xu (Journal of Hazardous Materials, 2026)

Modification of sheep hoof collagen by electron beam irradiation: Mechanistic insights into its effects on physicochemical and functional properties based on molecular structural analyses - Huiyu Han; Jing Xi; Jiangtao Yu; Lin Li; Shengqi Jiang; Rong Bai; Xiang Ye; Siying Wang; Hongqing Nie; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Irradiation co-succinylation modification of caprine casein: Impact on physicochemical properties, molecular structure, and functional properties - Jing Xi; Huiyu Han; Rong Bai; Madina Aitmagambetova; Siying Wang; Shengqi Jiang; Hongqing Nie; Lin Li; Xiang Ye; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

Ultrastructure and optical features of compound eyes in Odontothrips loti (Thysanoptera: Thripidae) - Xu Ding; Ya-Rong Gu; Bai-Long Yang; Ying Miao (Arthropod Structure & Development, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Crystal-facet regulation of SnO₂ {221} and {110} for selective detection of dimethyl carbonate and H2 gases in battery thermal runaway - Xun Shen; Aijun Yang; Ruochen Ding; Kehan Bo; Jifeng Chu; Pengxu Chen; Chenhui Li; Hongye Yuan; Huan Yuan; Mingzhe Rong; Xiaohua Wang (Chemical Engineering Journal, 2026)

Hydroxybutyl chitosan-based thermosensitive hydrogel enhanced osteoporotic bone regeneration through sustained release of alendronate and BMP-2 - Mingyuan Lei; Haibing Liu; Qiang Zhong; Libo Zhao; Jingwen Liu; Huaming Mai; Yuheng Zhang; Hongyu Wang; Yourong Chen; Rong Chen; Yixin Xu; Hao Li; et al. (Carbohydrate Polymers, 2026)

Cadmium accumulation and toxic effects on wheat under foliar and soil exposure to the simulated atmospheric deposition of cadmium - Mengling Huang; Xiuting Rong; Yuansong Ding; Xianlong Gao; Min Li; Xiaozhi Wang; Hailong Liu (Environmental Geochemistry and Health, 2026)

Preharvest melatonin application enhances soft rot resistance in kiwifruit through the jasmonic acid signaling pathway - Junsen Peng; Shufeng Du; Rong Fan; Youhua Long; Guofang Xie; Xiaochun Ding; Xiaoqing Dong (Postharvest Biology and Technology, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Unsupervised characterization of site conditions from detailed information for improved ground motion modeling - Qingxu Zhao; Mianshui Rong; Yi Ding; Jixin Wang; Bin Zhang; Xiaoshan Kong; Xiaojun Li (Engineering Geology, 2026)

Cd(II) adsorption at a biofilm–mineral interface: Capacity penalty, site masking, and behavior shifts induced by bacterial coating - Liangwei Han; Huijie Zheng; Zihao Ding; Yinjie Kang; Jiang Yu; Yineng Lu; Rong Tan; Zhuanjun Zhao (Chemical Engineering Journal, 2026)

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

Total Saponins of Panax Notoginseng Leaves Modulate the "Microglial-NLRP3/Caspase-1" Axis associated with Gut Microbial/SCFAs Alterations: Correlative Insights into Cognitive Improvement in Senescence - Lan Sun; Jiarong Du; Yuan Xu; Shanshan Wang; Yao Zhang; Rong Yuan; You Lv; Longyan Ding; Yanling Jin; Yu Ren; Xiaoman LV; Jiali Yuan; et al. (Molecular Neurobiology, 2026)

A novel multiplex RPA/CRISPR-Cas12a integrated biosensor for on-site detection of high-risk HPV genotypes - Yuying Bao; Wei Ding; Ling Zhang; Wei Wang; Jia Liu; Yiting Qu; Liguo Zhu; Kairui Zhang; Guanxi Zhong; Rong Han; Qiang Shen; Bo Wang; et al. (Analytica Chimica Acta, 2026)

Deep learning and UAV-Based image recognition for identification of medicinal plants in Gentiana Sect. Cruciata - Rong Ding; Jiangkai Yang; Tianyi Wang; Chenghui Wang; Xi Huang; Shihong Zhong; Rui Gu (Computers and Electronics in Agriculture, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Bi-mediated Z-scheme heterojunction of carbon-rich BiO2-X /Carbon nitride: Enabling a sensitive photoelectrochemical aptasensor for diazinon detection - Quan Shen; Rong Zhi; Song Zhang; Yi Ding; Jing Huang; Yuqi Chen; Keqiang Xu; Pengcheng Yan; Henan Li (Journal of Environmental Chemical Engineering, 2025)

MOF-derived Ce–Mn mixed oxide catalysts for efficient low-temperature NOx removal via NH3-SCR - Huiqin Ning; Xiahong Gao; Peilin Luo; Chengjin Ding; Rong Zeng; Shengjun Deng; Dan Zhao; Chao Chen; Shunmin Ding (Journal of Environmental Chemical Engineering, 2025)

Phosphorus removal in swine wastewater by lanthanum-modified biochar and its synergistic interaction with Pseudomonas sp. G16 - Rong Gao; Liu Lou; Tong Xu; Gang Liu; Jun Fang; Sujuan Ding (Journal of Environmental Chemical Engineering, 2025)

Sonodynamic interfacial-assisted photosensitizer disrupts lipid bilayer order to eradicate gram-negative bacteria using HB@ZIF-8 nanoparticles - Li Ding; Yiwen Xie; Xinrui Bai; Liang Qiu; Yerlan Zharykbasov; Zhainagul Kakimova; Gang Wu; Jianlong Wang; Yuxia Song; Rong Wang (Food Chemistry, 2025)

Application of modified biochar in constructed wetlands for efficient livestock wastewater treatment - Tong Xu; Rong Gao; Yu Yan; Jun Fang; Sujuan Ding (Environmental Research, 2025)

Langmuir/BET ratio as a quantitative indicator: Chain length-dependent adsorption modes of fillers regulating ion transport and high-voltage performance in PEO-based composite electrolytes - Ding Nan; Altan Bolag; Rong Zhang; Ji Qi; Bila Ga; Tana Bao; Wei Li; Lei Li (Chemical Engineering Journal, 2025)

Spon2 knockdown suppresses the phenotype of house dust mite-induced allergic asthma in mice and cells - Haihan Zheng; Shenggang Ding; Daoxiang Rong; Ting Li; Mei Xiong (Immunologic Research, 2025)

A new model for describing black holes based on the essential relationship between electric field and gravitational field analysis - Rong-Pei Ding; Zhi-Hua Zhu (Applied Geophysics, 2025)

Hydrothermal carbonization: A potent strategy for simultaneously eliminating ARGs-associated pollutants in livestock manure and blocking ARGs horizontal gene transfer - Sunlin Chi; Jinmei Xiao; Jinying Xu; Aijing Li; Jianhui Hu; Xinyi Wang; Meiyan Zhang; Wei Liu; Yalan Zhang; Huijun Ding; Jun Rong; Li Leng; et al. (Journal of Hazardous Materials, 2025)

Recent progress in DNA-based approaches for authenticating herbal materials and botanical dietary supplements - Rong Chen; Wenjun Song; Hongling Chen; Tongyi Peng; Huilin Li; Sheng Ding (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Fermentation-derived dihydroferulic acid from Cordyceps militaris binds AKT1 to protect intestinal epithelial health - Rong Huang; Jixing Gao; Zelin Wang; Jie Cai; Zhenjun Zhu; Qingping Wu; Juan Wang; Fen Zhang; Yu Ding (Food Bioscience, 2025)

Predicting thermal comfort of healthcare workers in hot environments based on machine learning algorithms - Song Wenfang; Yu Sijing; Liu Ziyu; Tang Rong; Ding Qiuyue; Zhou Shiqing; Wang Xiaolan (Energy and Buildings, 2025)

A durable immuno-protective core-shell microgel for the enhanced pancreatic islet transplantation in diabetes therapy - Zeming Hu; Yang Luo; Muhammad Junaid; Rong Xu; Yaoqi Chen; Jie Yao; Renhao Ni; Tong Zhu; Hua Zhang; Huiqing Ding; Yabin Zhu (Chemical Engineering Journal, 2025)

Compartment engineering in yeast: a path to increased biochemical production - Yuyang Wang; Liyan Cao; Lanxin Rong; Chen Ding; Chang Liu; Qingqing Ye; Qingeng Huang; Cui-ying Zhang; Ning Xu; Jiwei Mao; Jee Loon Foo; Aiqun Yu (Chemical Engineering Journal, 2025)

Confined Ostwald ripening approach towards highly durable and flexible 3D PTFE aerogels boosting Pickering emulsion separation in bi-phase photocatalysis - Yuxin Zhang; Jiawei Huangfu; Bin Rong; Xiongfei Du; Yang Hu; Xu Zeng; Kaikai Chen; Changkun Ding; Wenping Hu; Kuo Yuan; Qinglin Huang (Chemical Engineering Journal, 2025)

Direct oxidation of trace methane to formaldehyde under ambient conditions by piezo-photocatalytic synergy - Qiyu Zhang; Li Rong; Yue Jiang; Zhiping Zhu; Xiaochang Lin; Yongzhen Ding; Hongmin Dong; Dezhao Liu (Chemical Engineering Journal, 2025)

Tectonic thickening in stagnant to mobile lid transition facilitated the stabilization of Archean cratons - Ning Ding; Chris Hawkesworth; Xiao-Lei Wang; Rong-Feng Ge; Axel Hofmann; Jun-Yong Li (Chemical Geology, 2025)

Interploidy hybridization enhances floral phenotypic diversity of Iris × norrisii tetraploids via 2n pollon - Jiacheng Tang; Liya Ding; Yike Gao; Rong Liu; Jianhua Xiao; Yi Lv; Ziyi Wang; Qixiang Zhang (Euphytica, 2025)

Machine learning-assisted affinity ultrafiltration for bioactive natural products discovery:Application to screening of neuraminidase inhibitors from medicinal herbs - Menghan Chen; Shengyong Ding; Liqing Wang; Tongtong Jian; Yong Yang; Rong Rong (Analytica Chimica Acta, 2025)

Exploring the mechanism of volatile organic compounds in respiratory tract tumors based on network toxicology and molecular simulation - Ran Ding; Qi Quan; QianQian Dai; TingQiu Quan; Rong Huang; DeHuan Xie; ZhiQing Long (Science of The Total Environment, 2025)

Efficient NMR spectroscopy approach for the determination of the relative configuration of Δ5,6Δ11,12-jatrophane diterpenes and their chemotherapy sensitization activities - Wenjing Tian; Jie Li; Mi Zhou; Yanlan Yang; Yingting Lin; Guanghui Wang; Zhiping Zeng; Yuting Bian; Cuiling Sun; Rong Ding; Haifeng Chen (Phytochemistry, 2025)

Integrated Biofilm Modification and Transcriptional Analysis for Improving Fengycin Production in Bacillus amyloliquefaciens - Chun-Yang Cao; Zheng-Jie Hou; Ming-Zhu Ding; Geng-Rong Gao; Bin Qiao; Si-Yu Wei; Jing-Sheng Cheng (Probiotics and Antimicrobial Proteins, 2025)

Effects of mulches on greenhouse gas emissions and soil microbial communities in cabbage production - Rong Liang; Lei Mei; Xuelian Fan; Jiangxing Wu; Mouliang Xiao; Yongfu Li; Jina Ding; Li Wang; Jaloliddin Shavkiev; David R. Chadwick; Davey Jones; Zhaofeng Yuan; et al. (Journal of Hazardous Materials, 2025)

Different impacts of temperature and precipitation on vegetation net primary production of global marsh wetlands - Jiaqi Zhang; Meiling Zhao; Rong Ma; Mingming Feng; Chen Ding; Liyuan Wu; Xianguo Lu; Xiangjin Shen; Ming Jiang (Global and Planetary Change, 2025)

Carbon encapsulated Fe0/Fe oxides for heterogeneous electro-Fenton process: Promoting Fe(II) regeneration under nanoconfinement - Kun-Xiao Zhang; Ablajan Tunyaz; Guan-Nan Zhou; Rong-Rong Ding; Pei-Wen Zheng; Xiao-Cheng Liu; Hou-Yun Yang; Yang Mu (Chemical Engineering Journal, 2025)

Unraveling the diversity of bile acid modifications by integrative mass spectrometry approaches - Nan Xing; Yu-Fei Wang; Xue Ding; Hong-Li Tan; Yi-Fang Li; Guo-Xiang Sun; Rong-Rong He; Wan-Yang Sun (Science China Life Sciences, 2025)

Two new steroidal saponins from the roots and rhizomes of Helleborus thibetanus - Hao Wei; Xin Zhang; Chao Ding; Yuze Li; Ziqiang Wang; Xiaomei Song; Dongdong Zhang; Rong Lin (Natural Product Research, 2025)

Goethite-humic acid composites for multi-metal soil remediation: Mechanisms and environmental transformation - Xiangbang Ma; Ram Proshad; Yineng Lu; Rong Tan; Zihao Ding; Geng Cheng; Ziyi Li; Shuangting Zhang; Zhuanjun Zhao (Journal of Environmental Chemical Engineering, 2025)

Facile fabrication of ethyl cellulose/gelatin fibers incorporated with copper-based metal-organic frameworks as humidity-triggered release of carvacrol for blueberry preservation - Jing Xie; Xingyu Rong; Xiaoqian Jiang; Yuping Zhao; Tianhua Ding; Jing Yan; Suqing Li; Wen Qin; Mingrui Chen; Yaowen Liu (Food Chemistry, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Oligosaccharide glycosylation of pigskin collagen: Impact on molecular structure, physicochemical properties, and gel functionality - Shengqi Jiang; Huiyu Han; Madina Aitmagambetova; Aidana Rakhimova; Lin Li; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Jing Xi; Wu Ding (Food Hydrocolloids, 2025)

Type-A and -C response regulator genes positively impact rice plant height and panicle architecture - Chenyu Rong; Renren Zhang; Jing Xie; Jieru Li; Tiantian Yan; Ziyu Liu; Yuexin Liu; Ruihan Xu; Xi’an Shi; Xuebin Zhao; Jiali Song; Yayi Meng; et al. (Plant Cell Reports, 2025)

An N-heterocyclic carbene-copper(I) functionalized metal-organic framework: Synthesis and recoverable applications in the carboxylation of CO2 with terminal alkynes - Li-Xin You; Tian-Cheng Han; Jin-Rong Li; Jie Guo; Gang Xiong; Fu ding; Ya-Guang Sun (Journal of Environmental Chemical Engineering, 2025)

Enhanced phosphate removal by lanthanum functionalization using zirconium-based metal organic frameworks: Role of in situ formed La(OH)3 - Suyu Kong; Meili Ding; Mengjiao Yu; Wei Rong; Yang Wang; Jianfeng Yao (Journal of Environmental Chemical Engineering, 2025)

Mechanistic study of ultrasound synergy with soybean 11S globulin to improve myofibrillar protein gel properties in low-salt lamb: molecular conformation and water migration - Rong Bai; Jing Xi; Huiyu Han; Rakhimova Aidana; Aitmagambetova Madina; Shengqi Jiang; Xiang Ye; Chunjie Yang; Siying Wang; Wu Ding (Food Research International, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Automatic assessment of fuel load and fire risk via digitized database and intelligent computer vision - Yifei Ding; Rong Deng; Yuxin Zhang; Xinyan Huang; Negar Elhami-Khorasani; Thomas Gernay (Process Safety and Environmental Protection, 2025)

Preparation of sodium alginate/pectin/cellulose nanofibrils films containing black soybean seed coat anthocyanins for monitoring goat meat freshness - Siying Wang; Xinyue Han; Ya Chen; Yikai Shao; Jiaqing Song; Chunjie Yang; Shengqi Jiang; Rong Bai; Xiang Ye; Wu Ding (Food Control, 2025)

Au-isolated Pt active site with enhanced C-H bond activation ability for selective oxidation of polyol to hydroxyl acid - Xuewei Ding; Ying Liao; Rong Fan; Hao Yan; Xin Zhou; Xiang Feng; Xiaobo Chen; Hui Zhao; Yibin Liu; Chaohe Yang (Chemical Engineering Journal, 2025)

Pyroptosis was suppressed by 20-hydroxyecdysone through Lin28b-mediated let-7d in vascular endothelial cells - Danli Chen; Jianjun Yang; Lingxuan Ren; Zihan Zheng; Zhen Jin; Jiazheng Wen; Jianyu He; Rongcheng Ding; Jianjiang Wang; Rong Lin; Qiang Song (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Development of a multiplex PCR assay for detection of Riemerella anatipestifer serotype 1 and serotype 2 strains - Mengsi Wu; Rong Guo; Meitong Chen; Min Zhu; Zongchao Chen; Chan Ding; Shengqing Yu (Veterinary Microbiology, 2025)

Petrogenesis and age of granitoids associated with the Dongshan Cu polymetallic deposit, East Kunlun Orogenic Belt, NW China: Implications for the Middle to Late Triassic tectonic setting and Cu polymetallic mineralization - Yi-Chen Chen; Zheng-Jiang Ding; Jun-Wei Bo; Shi-Jiong Han; Ting-Ting Li; Pan Ji; Rong-Qiang Guo (Geochemistry, 2025)

Micromotors assisted in vivo dopamine polymerization for anti-tumor therapy - Dailing Du; Ye Feng; Miaomiao Ding; Jinghui Rong; Bin Chen; Chao Gao; Tingting Jiang; Yingfeng Tu; Fei Peng (Chemical Engineering Journal, 2025)

Current Status and Progress in Stem Cell Therapy for Intracerebral Hemorrhage - Ning Ding; Ran Luo; Qian Zhang; Huanhuan Li; Shuixian Zhang; Huanran Chen; Rong Hu (Translational Stroke Research, 2025)

Perspectives on the application of remote sensing technology in the cultivation of medicinal plants - Liwen Zhong; Xuemei Wu; Rong Ding; Chenghui Wang; Ling Li; Jieling Zhang; Jie Zhang; Rui Gu; Shihong Zhong (International Journal of Remote Sensing, 2025)

Voagafries A–E, undescribed indole alkaloids with anti-glioma activity from Voacanga africana - Cai-Feng Ding; Ma-Long Qin; Kun-Ying Zhao; Wen Gao; Shan-Ze Yin; Xian-Guang Hu; Gui-Guang Cheng; Rong-Ping Zhang; Wei-Yan Hu (Phytochemistry, 2025)

Characterization of a stable QTL for quality-related traits and its effects on yields in wheat (Triticum aestivum L.) - Hongke Ding; Yankun Li; Jinlian Ou; Yuanze Song; Lihua Qiu; Xinyu Rong; Han Sun; Chunhua Zhao; Yongzhen Wu; Ran Qin; Jinlong Li; Cheng Liu; et al. (Theoretical and Applied Genetics, 2025)

Adipose-mesenchymal stem cell-derived extracellular vesicles enhance angiogenesis and skin wound healing via bFGF-mediated VEGF expression - Yonghu Ding; Mengsheng Song; Rong Huang; Weiting Chen (Cell and Tissue Banking, 2025)

Fusion of multiple photogrammetric DEMs for large-scale lunar topographic mapping - Rong Huang; Wenhui Ding; Yusheng Xu; Zhen Ye; Siyan Xu; Miyu Zhou; Xiaohua Tong (Advances in Space Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Assessing the interaction of oceanic and riverine processes on coastal phytoplankton dynamics in the East China Sea - Jiawei Gao; Rong Bi; Julian P. Sachs; Yaoyao Wang; Yang Ding; Hong Che; Jing Zhang; Peng Yao; Jie Shi; Meixun Zhao (Marine Life Science & Technology, 2025)
The interaction of riverine inputs and ocean current systems causes complex spatiotemporal variations in phytoplankton dynamics in marginal seas of the northwest Pacific Ocean, yet quantitative assessments of these variations and their causes remain limited. Here we evaluate phytoplankton biomass and community structure changes using lipid biomarkers, accompanying ocean circulation and nutrient variations in surface waters collected in spring and summer of 2017–2018 at 118 sites in the East China Sea off the Zhejiang coast. High biomass of diatoms, inferred from brassicasterol concentrations, shifted from the south in spring to the north in summer, while high dinoflagellate biomass, inferred from dinosterol concentrations, occurred mainly in the Changjiang (Yangtze) River plume and adjacent areas in both seasons. Seasonal variation in phytoplankton distribution was linked to the spatial extents of water masses such as the Changjiang Diluted Water (CDW) and the intrusion of the Kuroshio Subsurface Water (KSSW). A three end-member mixing model was applied to quantify water mass contributions. The results showed that an increase in the KSSW (from 0 to 40%) and a decrease in the CDW (from 100 to 20%) resulted in a significant (20%) increase in diatom proportions and a significant (20%) decrease in dinoflagellate proportions. Dinoflagellate proportions were highest in the CDW-dominated region, while diatoms and total phytoplankton biomass were higher in the CDW–KSSW mixing region and the KSSW-dominated region. This study highlights the dynamic response of the phytoplankton community to water mass changes in marginal seas that can aid coastal ecosystem management.

Combination of herbal extracts regulates growth performance, liver and intestinal morphology, antioxidant capacity, and intestinal microbiota in Acrossocheilus fasciatus - Yi Ting Shen; Zhi Li Ding; Xiao Yan Wang; Wen Qi Chen; Rong Xing Xia; Shun Yang; Hui Fei (Aquaculture, 2025)

CSF multi-omics of intracerebral hemorrhage from onset to reperfusion underscores lipid metabolism in functional outcome - Yibin Jiang; Sin Man Lam; Shuixian Zhang; Huan Miao; Yong Zhou; Qian Zhang; Tengyuan Zhou; Hui Feng; Ning Ding; Haomiao Wang; Ran Luo; Yi Yin; et al. (Science Bulletin, 2025)

Machine learning models with innovative outlier detection techniques for predicting heavy metal contamination in soils - Ram Proshad; S.M. Asharaful Abedin Asha; Rong Tan; Yineng Lu; Md Anwarul Abedin; Zihao Ding; Shuangting Zhang; Ziyi Li; Geng Chen; Zhuanjun Zhao (Journal of Hazardous Materials, 2025)

Lipid biomarkers indicate the dynamics of particulate organic carbon and its carbon sequestration effects during the degradation of Ulva prolifera - Miaomiao Zhao; Hongmei Li; Rong Bi; Hailong Zhang; Shengrong Huang; Li Li; Yang Ding; Yongyu Zhang; Meixun Zhao (Marine Pollution Bulletin, 2024)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

Deciphering the role of biochar pseudocapacitance strengthening in promoting syntrophic methanogenesis: Microbial capacitance-tropism in propionate metabolism - Danyang Zhao; Lizi Ding; Xuemeng Wang; Qian Li; Feixiang Zan; Yu-You Li; Rong Chen (Chemical Engineering Journal, 2024)

Facile engineering of metal–organic framework derived SnO2@NiO core–shell nanocomposites based gas sensor toward superior VOCs sensing performance - Hui Xu; Haoran Zhong; Jinwu Hu; Xianjun Rong; Wenhui Zhang; Yinsheng Wang; Shengjuan Li; Guisheng Li; Ding Wang (Chemical Engineering Journal, 2024)

Characterization and expression analysis of the MADS-box gene AGL8 in cotton: insights into gene function differentiation in plant growth and stress resistance - Zhicheng Wang; Yuefen Cao; Yurong Jiang; Mingquan Ding; Junkang Rong (Molecular Biology Reports, 2024)

The GaKAN2, a KANADI transcription factor, modulates stem trichomes in Gossypium arboreum - Xujiao Ren; Luying Yang; Yasir Muhammad; Yuxing Xie; Xinyi Lin; Li Yu; Yuefen Cao; Mingquan Ding; Yurong Jiang; Junkang Rong (Molecular Genetics and Genomics, 2024)

Unraveling fertilization effects on the dynamics of arbuscular mycorrhizal fungal community in the Qinghai-Tibet Alpine Meadow - Longfei Liu; Yi Ren; Shuo Sun; Chen Liu; Kairui Ding; Rong Li; Pengfei Zhang; Biao Shen; Mohammadhossein Ravanbakhsh; Wu Xiong; Qirong Shen (Soil Ecology Letters, 2024)

Exploring secretory signal sequences useful in excreting recombinant proteins in Beauveria bassiana as biocontrol fungus - Kang Wei; Jin-Li Ding; Hang-Rong Xu; Ming-Guang Feng; Sheng-Hua Ying (Archives of Microbiology, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

Biodegradable MAM-based amphiphilic block copolymers: Toward efficient and eco-friendly kinetic inhibitors for methane hydrate formation - Li Wan; Xiang-Long Ding; Ai-Xiang Liu; Hao Cui; Jin-Rong Zhong; Yi-Min Dai (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Bioactives from biomass: Treasure for future potent antimicrobial applications - Weicheng Chen; Peng Zhang; Yucui Ding; Xiaobin Xie; Jianlong Fu; Rong Zhao; Yihan Xiao; Miodrag J. Lukic; Bin Li; Weishan Wang; Song Chen (Chemical Engineering Journal, 2024)

Research on fault diagnosis of electric gate valve in nuclear power plant based on the VMD-MDI-ISSA-RF model - Jia-rong Gao; Yong-kuo Liu; Cheng-jie Duan; Peng Ding; Ju-qing Song (Annals of Nuclear Energy, 2024)

County-level carbon budget and carbon compensation in the Yellow River Basin: a perspective with balancing efficiency and equity - Zhixiang Xie; Lu Wang; Rongqin Zhao; Liangang Xiao; Minglei Ding; Shuangsheng Yao; Xiaowei Chuai; Peijun Rong (Environment, Development and Sustainability, 2024)

Recent advances and perspectives of biochar for livestock wastewater: Modification methods, applications, and resource recovery - Rong Gao; Sujuan Ding; Zhuangzhuang Liu; Hongmei Jiang; Gang Liu; Jun Fang (Journal of Environmental Chemical Engineering, 2024)

Low oxygen adsorption energy barrier architectures to facilitate microenvironmental photocatalytic disinfection in Wei River - Lenan Yao; Yunyan Bai; Li Ding; Yayun Hu; Zuwang Zhang; Yajie Zhang; Rui Chen; Haijiao Xie; Jianlong Wang; Rong Wang (Chemical Engineering Journal, 2024)

An investigation of a self-powered low-frequency nonlinear vibration isolation system - Ze-Qi Lu; Rong-Biao Hao; Dao Wu; Hu Ding; Li-Qun Chen (Engineering Structures, 2024)

Electric field induced molecular orientation to construct the composite polymer electrolytes with vertically aligned ion diffusion pathways for stable solid-state lithium metal batteries - Yuanjun Zhao; Mengqiu Gao; Yanyang Qin; Xinyu Da; Xuetian Deng; Xin Jia; Kai Xi; Yaqiong Su; Shujiang Ding; Qiang Rong; Xiangpeng Kong; Guoxin Gao (Chemical Engineering Journal, 2024)

Uncovering the evolution of ozone pollution in China: A spatiotemporal characteristics reconstruction from 1980 to 2021 - Su Ding; Zhiwei Wei; Shuiling Liu; Rong Zhao (Atmospheric Research, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

Sustainable design of photo-Fenton-like oxidation process in actual livestock wastewater through the highly dispersed FeCl3 anchoring on a g-C3N4 substrate - Yanfang Feng; Yunyi Liang; Chenman Ding; Yue Jiang; Hongmei Jin; Shaopeng Rong; Jun Wu; Shiying He; Changlei Xia; Lihong Xue (Water Research, 2024)

Exendin-4, a glucagon-like peptide-1 receptor agonist, alleviates muscular dysfunction and wasting in a streptozotocin-induced diabetic mouse model compared to metformin - Ding-Cheng Chan; Yuan-Cheng Lin; Huei-Ping Tzeng; Rong-Sen Yang; Meng-Tsan Chiang; Shing-Hwa Liu (Tissue and Cell, 2024)

Self-heating photothermal synergistic catalytic decomposition of carcinogenic formaldehyde by α-MnO2 at ambient temperature: Functional roles of surface acidic-basic sites - Danni Ding; Zeyi Cheng; Yu Zhou; Nan Zhang; Wang Ran; Shaopeng Rong (Journal of Environmental Chemical Engineering, 2024)

FOXP4-AS1 promotes CD8+ T cell exhaustion and esophageal cancer immune escape through USP10-stabilized PD-L1 - Guo-yi Shen; Yi Zhang; Rong-zhi Huang; Zhi-yong Huang; Le-yi Yang; Ding-zhu Chen; Shao-bin Yang (Immunologic Research, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Organic-mineral colloids regulate the migration and fractionation of rare earth elements in groundwater systems impacted by ion-adsorption deposits mining in South China - Xiao-Rui Liu; Wen-Shen Liu; Miaoyue Zhang; Chao Jin; Keng-Bo Ding; Alan J.M. Baker; Rong-Liang Qiu; Ye-Tao Tang; Shi-Zhong Wang (Water Research, 2024)

Intestinal microbiota via NLRP3 inflammasome dependent neuronal pyroptosis mediates anxiety-like behaviour in mice exposed to 3.5 GHz radiofrequency radiation - Gui-qiang Zhou; Xing Wang; Peng Gao; Tong-zhou Qin; Ling Guo; Zhao-wen Zhang; Zhi-fei Huang; Jia-jin Lin; Yun-tao Jing; Hao-nan Wang; Chun-ping Wang; Gui-rong Ding (Science of The Total Environment, 2024)

A dual-mode fluorescence and colorimetric sensing platform for efficient detection of ofloxacin in aquatic products using iron alkoxide nanozyme - Xiaodan Ding; Waqas Ahmad; Yawen Rong; Jizhong Wu; Qin Ouyang; Quansheng Chen (Food Chemistry, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

CsSHMT3 gene enhances the growth and development in cucumber seedlings under salt stress - Zhuohui Zhang; Xuemei Hou; Rong Gao; Yihua Li; Zhiqi Ding; Yi Huang; Kangding Yao; Yandong Yao; Cheng Liang; Weibiao Liao (Plant Molecular Biology, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Vertical distributions of lipid biomarkers in spring and summer in coastal regions of the East China Sea - Jiawei Gao; Shulan Xu; Rong Bi; Yaoyao Wang; Yang Ding; Hong Che; Jing Zhang; Peng Yao; Jie Shi; Meixun Zhao (Frontiers in Marine Science, 2024)
Lipid biomarkers are amongst the most widely used proxies in studies of the structure and functioning of marine food webs. However, vertical distributions of lipid biomarkers and their controlling mechanisms remain unclear, especially in highly dynamic coastal ecosystems. Here we tested vertical profiles of key lipid biomarkers (sterols and fatty acids) in suspended particles and their correlations with water masses in spring of 2017 and summer of 2018 in the Zhejiang coasts of the East China Sea. The Changjiang Diluted Water, the Taiwan Strait Water and the Kuroshio Subsurface Water showed strong contributions in the surface layer in spring, the surface layer in summer, and the deep layer in both seasons, respectively. Accordingly, lipid biomarker composition also varied between different water layers. Overall, lipid biomarker concentrations in the surface layer were around 2 ~ 7 times higher than those in the deep layer, indicating high phytoplankton biomass in the surface layer. The ratio of docosahexaenoic acid to eicosapentaenoic acid was also higher in the surface layer, especially in the south of our study region, suggesting high nutritional quality of particulate organic matters in the surface layer. Significant correlations between the depth profiles of lipid biomarkers and water masses suggested the control of water masses on lipid biomarker production. The distribution patterns of lipid biomarkers in our study are consistent with previous findings on zooplankton grazing and fish larvae, highlighting the significance of lipid biomarkers as trophic markers to study food web structure and functioning in highly dynamic coasts.

New diterpenoid alkaloids from Delphinium pachycentrum Hemsl - Yuan-Feng Yan; Ya-Rong Wang; Hong-Jun Jiang; Zong-Bao Ding; Tian-Peng Yin (Natural Product Research, 2024)

Guided isolation of enantiomeric lignans from Cimicifuga heracleifolia Kom. by antioxidant activity and molecular networking - Yanwen Sun; Liyi Chen; Yan Zhou; Fei Han; Yifang Rong; Liqin Ding; Feng Qiu (Phytochemistry, 2024)

Biodegradation of various grades of polyethylene microplastics by Tenebrio molitor and Tenebrio obscurus larvae: Effects on their physiology - Meng-Qi Ding; Jie Ding; Zhi-Rong Zhang; Mei-Xi Li; Chen-Hao Cui; Ji-Wei Pang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu; Shan-Shan Yang (Journal of Environmental Management, 2024)

Modifying duck myofibrillar proteins using sodium bicarbonate under cold plasma treatment: Impact on the conformation, emulsification, and rheological properties - Shengqi Jiang; Chunjie Yang; Rong Bai; Ziwei Li; Linlu Zhang; Ya Chen; Xiang Ye; Siying Wang; Hao Jiang; Wu Ding (Food Hydrocolloids, 2024)

Straw management adopted by large farms sustains grain yield but mitigates greenhouse gas emissions - Zhenzhen Li; Yong Lin; Zheng-Rong Kan; Sana ur Rehman; Atta Mohi Ud Din; Feng-Min Li; Shixiang Zhang; Ping Wu; Yingfu Ding; Chensheng Xu; Congying Rao; Huaxin Dai; et al. (Field Crops Research, 2024)

Phosphorylated covalent organic framework/graphene composites for photoelectrothermal integrated collaborative reduction of uranium - Rui Zhang; Liang Tao; Cheng-Peng Niu; Cheng-Rong Zhang; Tie-Ying Shi; Xiao-Xing Wang; Ying-Ao Wang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Machine learning assisted combined systems of wastewater treatment plants with constructed wetlands optimal decision-making - Wei Dai; Ji-Wei Pang; Ying-Jun Zhao; Jie Ding; Han-Jun Sun; Hai Cui; Hai-Rong Mi; Yi-Lin Zhao; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Purine permease (PUP) family gene PUP11 positively regulates the rice seed setting rate by influencing seed development - Chenyu Rong; Renren Zhang; Yuexin Liu; Zhongyuan Chang; Ziyu Liu; Yanfeng Ding; Chengqiang Ding (Plant Cell Reports, 2024)

Seed germination and seedling growth response of Leymus chinensis to the allelopathic influence of grassland plants - Kaili Wang; Pengpeng Dou; Zhengzhou Miao; Jing Huang; Qian Gao; Lizhu Guo; Kesi Liu; Yuping Rong; Ding Huang; Kun Wang (Oecologia, 2024)

Population pharmacokinetics and pharmacodynamics of efmarodocokin alfa (IL-22Fc) - Yanke Yu; Michael E. Rothenberg; Han Ting Ding; Ari Brekkan; Gizette Sperinde; Brandon Harder; Rong Zhang; Ryan Owen; Nastya Kassir; Annemarie N. Lekkerkerker (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Seismic performance and estimation of flexural bearing capacity of prefabricated engineered cementitious composite shell–reinforced concrete composite column with grouted sleeve connection - Mengjia Ding; Weibing Xu; Jin Wang; Yanjiang Chen; Rong Fang; Daxing Zhou; Liqun Hou; Yulong Sun (Soil Dynamics and Earthquake Engineering, 2024)

Susceptibility and exposure risk to airborne aerosols in intra-urban microclimate: Evidence from subway system of mega-cities - Zhijian Liu; Mingtao Ding; Chenxing Hu; Rui Rong; Chaofan Lin; Guangpeng Yao; Xuqiang Shao; Guangya Jin (Science of The Total Environment, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Negative thermopower anisotropic ionic thermoelectric hydrogels based on synergistic coordination and hydration for low-grade heat harvesting - Luzheng Chen; Xuhui Rong; Zhuqing Liu; Qijun Ding; Xia Li; Yifei Jiang; Wenjia Han; Jiang Lou (Chemical Engineering Journal, 2024)

A novel method for in situ imaging of root exudates and labile elements reveals phosphorus deficiency-induced mobilization of rare earth elements in the rhizosphere of Phytolacca americana - Chong Liu; Ting-Xuan Ding; Antony van der Ent; Chang Liu; Jean Louis Morel; Catherine Sirguey; Wen-Shen Liu; Ye-Tao Tang; Rong-Liang Qiu (Plant and Soil, 2024)

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

Soil moisture dynamics regulates the release rates and lability of copper in contaminated paddy soils - Yijin Lv; Jialiang Kuang; Zecong Ding; Rong Li; Zhenqing Shi (Science of The Total Environment, 2024)

Degradation of low-density polyethylene by the bacterium Rhodococcus sp. C-2 isolated from seawater - Zhen Rong; Zhi-Hao Ding; Yue-Hong Wu; Xue-Wei Xu (Science of The Total Environment, 2024)

The impact of extreme precipitation on physical and biogeochemical processes regarding with nutrient dynamics in a semi-closed bay - Rushui Xiao; Guandong Gao; Dezhou Yang; Ying Su; Yang Ding; Rong Bi; Shibo Yan; Baoshu Yin; Shengkang Liang; Xianqing Lv (Science of The Total Environment, 2024)

Investigation on the mechanism of solvothermal extraction of coals by macromolecular models - Hongyi Kang; Jingxiu Wang; Fusong Chen; Tao Rong; Yuanhao Yu; Wang Ding; Haibin Zuo (Fuel, 2024)

Untargeted metabolomics analysis of non-volatile metabolites and dynamic changes of antioxidant capacity in Douchi with edible mushroom by-products - Pei-Xiu Rong; Xiao-Qin He; Mutamed Ayyash; Yi Liu; Ding-Tao Wu; Fang Geng; Hua-Bin Li; Siew Bee Ng; Hong-Yan Liu; Ren-You Gan (Food Chemistry, 2024)

Interfacial coordination-assisted construction of mechanically robust, fluorescent and intumescent flame retardant epoxy resins - Xin-Miao Li; Wei-Bin Bai; Yu-Cai Lin; Fu-Chuan Ding; Rong-Kun Jian (Chemical Engineering Journal, 2024)

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

Engineered hydrochar from waste reed straw for peroxymonosulfate activation to degrade quinclorac and improve solanaceae plants growth - Chunxia Ding; Can Ye; Wei Zhu; Guangyong Zeng; Xuemei Yao; Yu Ouyang; Jie Rong; Yaping Tao; Xiangying Liu; Yaocheng Deng (Journal of Environmental Management, 2023)

Super-stretching and high-performance ionic thermoelectric hydrogels based on carboxylated bacterial cellulose coordination for self-powered sensors - Luzheng Chen; Jiang Lou; Xuhui Rong; Zhuqing Liu; Qijun Ding; Xia Li; Yifei Jiang; Xingxiang Ji; Wenjia Han (Carbohydrate Polymers, 2023)

Efficacy of pterostilbene suppression on Aspergillus flavus growth, aflatoxin B1 biosynthesis and potential mechanisms - Yong-Mei Hu; Yi-Rong Wang; Wen-Bin Zhao; Yan Yan Ding; Zheng-Rong Wu; Guang-Han Wang; Peng Deng; Shao-Yong Zhang; Jun-Xia An; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (International Journal of Food Microbiology, 2023)

Efficient removal of uranium under strong acid based on charge separation and protonation coupled covalent organic frameworks - Shun-Mo Yi; Cheng-Rong Zhang; Xin Liu; Xiao-Juan Chen; Jia-Xin Qi; Cheng-Peng Niu; Jin-Lan Liu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Blockade of the Dopamine D3 Receptor Attenuates Opioids-Induced Addictive Behaviours Associated with Inhibiting the Mesolimbic Dopamine System - Rong-Rong Hu; Meng-Die Yang; Xiao-Yan Ding; Ning Wu; Jin Li; Rui Song (Neuroscience Bulletin, 2023)

Quantification of multiple environmental controls on lipid biomarkers in common marine diatoms and dinoflagellates - Zhong Cao; Rong Bi; Chuanli Zhang; Jiaxuan Cui; Li Li; Yang Ding; Meixun Zhao (Marine Biology, 2023)

Hydrogeochemical characterization and precursor anomalies of hot springs in the North Tianshan orogen - Zhihua Ding; Xiaocheng Zhou; Chengguo Wang; Jingchao Li; Miao He; Jiao Tian; Kayimu Saimaiernaji; Chengying Zhu; Wei Yan; Rong Ma; Xinyong Li; Na Li; et al. (Applied Geochemistry, 2023)

Positive relationships between species diversity and genetic diversity on a local scale at Mt. Wu Yi, China - Lei Xie; YueYao Feng; Rong Zhao; Ting Lv; NingJie Wang; Yao Li; Xiao Zheng; ShuiFei Chen; Hui Ding; YanMing Fang (Biodiversity and Conservation, 2023)

Association between vitamin D supplementation and cancer incidence and mortality: A trial sequential meta-analysis of randomized controlled trials - Zhangyou Guo; Ming Huang; Dandan Fan; Yuan Hong; Min Zhao; Rong Ding; Yao Cheng; Shigang Duan (Critical Reviews in Food Science and Nutrition, 2023)

Surface acidic sites strengthened core-shell HC@MnO2 for enhanced gaseous ammonia adsorption - Weijiang He; Jingling Lu; Nan Zhang; Yu Zhou; Danni Ding; Yanfang Feng; Shaopeng Rong (Chemosphere, 2023)

Disinfection by-product precursors introduced by sandstorm events: Composition, formation characteristics and potential risks - Zhenqi Du; Shunke Ding; Rong Xiao; Chao Fang; Ruibao Jia; Wenhai Chu (Water Research, 2023)

Ferrous ion enhanced Fenton-like degradation of emerging contaminants by sulfidated nanosized zero-valent iron with pH insensitivity - Jia-Qi Chen; Guan-Nan Zhou; Rong-Rong Ding; Qi Li; Han-Qing Zhao; Yang Mu (Journal of Hazardous Materials, 2023)

Effect of PM2.5 air pollution on the global burden of lower respiratory infections, 1990–2019: A systematic analysis from the Global Burden of Disease Study 2019 - Junjie Hu; Runxuan Zhou; Rong Ding; Da-Wei Ye; Yanbing Su (Journal of Hazardous Materials, 2023)

The Comparison of Temporal Transcriptome Changes Between Morning-Opening and Afternoon-Opening Iris Flowers Reveals the Candidate Genes Regulating Flower Opening and Closing - Rong Liu; Yike Gao; Chunjing Guan; Liya Ding; Zhuping Fan; Qixiang Zhang (Journal of Plant Biology, 2023)

P24-42: A new generation of fully human anti-CTLA-4 heavy chain-only, Porustobart, shows superior safety in nonclinical study and clinical trials - J. Rong; L. Ding; F. Chen; J. Zhao; Y. He; Y. Rong; V. Chen (Toxicology Letters, 2023)

ML based approach for inverting penetration depth of SAR signals over large desert areas - Jun Zhu; Guanxin Liu; Rong Zhao; Xiaoli Ding; Haiqiang Fu (Remote Sensing of Environment, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

Electrospun polyvinyl alcohol-chitosan dressing stimulates infected diabetic wound healing with combined reactive oxygen species scavenging and antibacterial abilities - Haibing Liu; Rong Chen; Pinkai Wang; Jinlang Fu; Zinan Tang; Jiajun Xie; Yanhong Ning; Jian Gao; Qiang Zhong; Xin Pan; Ding Wang; Mingyuan Lei; et al. (Carbohydrate Polymers, 2023)

Enhancing fengycin production in the co-culture of Bacillus subtilis and Corynebacterium glutamicum by engineering proline transporter - Geng-Rong Gao; Si-Yu Wei; Ming-Zhu Ding; Zheng-Jie Hou; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng; Ying-Jin Yuan (Bioresource Technology, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

One new elemane sesquiterpenoid glycoside and five glycoglycerolipids from Pittosporum truncatum with anti-bacterial activity - Rong Huang; Ji-Li Deng; Sheng-Nan Guan; Jia-Qi Ding; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

A new butenolide with antifungal activity from solid co-cultivation of Irpex lacteus and Nigrospora oryzae - Ya-Mei Wu; Xue-Qiong Yang; Jing-Xin Chen; Ting Wang; Tai-Ran Li; Fan-Rong Liao; Run-Tong Liu; Ya-Bin Yang; Zhong-Tao Ding (Natural Product Research, 2023)

Detection and quantification of cotton trichomes by deep learning algorithm - Keyan Luo; Yu Jin; Shuhan Wen; Yicheng Li; Junkang Rong; Mingquan Ding (Computers and Electronics in Agriculture, 2023)

RETRACTED: Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2023)

Ergostane-type sterols and sesquiterpenes with anti-neuroinflammatory activity from a Nigrograna species associated with Clematis shensiensis - Liang-Liang Zhai; Ting-Ting Jiang; Rong Zhang; Jian-Nan Li; Yi-Jie Zhai; Qiang Zhang; Ding Li; Wen-Bo Han (Phytochemistry, 2023)

Identification and characterization of goat milk key flavor compounds and their precursors in electron beam irradiation and pasteurization on raw - Chunlu Wen; Ya Chen; Madina; Linlu Zhang; Yue Peng; Bai Rong; Linjie Xi; Shengqi Jiang; Jiangtao Yu; Junqing Bai; Niu Wei; Li Kui; et al. (Innovative Food Science & Emerging Technologies, 2023)

Behaviour of bamboo scrimber I-beam-box-column connections under static loads - Shao-Bo Kang; Jie-Xin Ding; Jun Xiong; Shu-Rong Zhou; Bin Long (Engineering Structures, 2023)

Four anti-inflammatory aromadendrane sesquiterpenoid fucosides and other constituents from Pittosporum glabratum var. neriifolium - Bai-Tong Sha; Rong Huang; Qiang-Guo Zhang; Sheng-Nan Guan; Jia-Qi Ding; Xin-Zheng Liu; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Identification of key precursors contributing to the formation of CX3R-type disinfection by-products along the typical full-scale drinking water treatment processes - Xu Yang; Shunke Ding; Rong Xiao; Pin Wang; Zhenqi Du; Ruihua Zhang; Wenhai Chu (Journal of Environmental Sciences, 2023)

Variations in the motility and biofilm formation abilities of Escherichia coli O157:H7 during noodle processing - Xiaohua He; Heer Ding; Zenghui Gao; Xiaofeng Zhang; Rong Wu; Ke Li (Food Research International, 2023)

Construction of α-MnO2/g-C3N4 Z-scheme heterojunction for photothermal synergistic catalytic decomposition of formaldehyde - Nan Zhang; Weijiang He; Zeyi Cheng; Jingling Lu; Yu Zhou; Danni Ding; Shaopeng Rong (Chemical Engineering Journal, 2023)

Understanding the nexus between environmental, social, and governance (ESG) and financial performance: evidence from Chinese-listed companies - Rong Zhou; Jundong Hou; Fei Ding (Environmental Science and Pollution Research, 2023)

Enhancement of acidic sites in layered MnO2 for the highly efficient selective catalytic oxidation of gaseous ammonia - Yu Zhou; Shaopeng Rong; Huifang Xie; Yanfang Feng; Danni Ding; Weijiang He; Nan Zhang; Jingling Lu (Journal of Environmental Chemical Engineering, 2023)

Kuroshio Intrusion Combined with Coastal Currents Affects Phytoplankton in the Northern South China Sea Revealed by Lipid Biomarkers - Yaoyao Wang; Rong Bi; Jiawei Gao; Hailong Zhang; Li Li; Yang Ding; Gui’e Jin; Meixun Zhao (Journal of Ocean University of China, 2023)

Process parameters and biological mechanism of efficient removal of Cd(II) ion from wastewater by a novel Bacillus subtilis TR1 - Zhongbing Wang; Rong Tan; Jie Gong; Baichuan Gong; Qian Guan; Xue Mi; Di Deng; Xiangning Liu; Chunli Liu; Chunjian Deng; Chunlian Ding; Guisheng Zeng (Chemosphere, 2023)

Anthropogenic activity and millennial climate variability affect Holocene mercury deposition of an alpine wetland near the largest mercury mine in China - Haijun Peng; Yimeng Rong; Di Chen; Ruiyang Sun; Jie Huang; Hanwei Ding; Carolina Olid; Haiyu Yan (Chemosphere, 2023)

Olefin-linked cationic covalent organic frameworks for efficient extraction of ReO4−/99TcO4− - Wei-Rong Cui; Wei Xu; Yi-Ru Chen; Kai Liu; Wei-Bin Qiu; Yibao Li; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Bipyridine-mediated fluorescence charge transfer process based on copper ion grafted upconversion nanoparticle platform for ciprofloxacin sensing in aquatic products - Xiaodan Ding; Waqas Ahmad; Jizhong Wu; Yawen Rong; Qin Ouyang; Quansheng Chen (Food Chemistry, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Exploring the potential anti-Alzheimer disease mechanisms of Alpiniae Oxyphyliae Fructus by network pharmacology study and molecular docking - Rong-Rong Zhen; Yan-Jie Qu; Li-Min Zhang; Chao Gu; Min-Rui Ding; Lei Chen; Xiao Peng; Bing Hu; Hong-Mei An (Metabolic Brain Disease, 2023)

The emergence of novel macrolide resistance island in Macrococcus caseolyticus and Staphylococcus aureus of food origin - Feng Zhang; Shi Wu; Jingsha Dai; Jiahui Huang; Jumei Zhang; Miao Zhao; Dongli Rong; Yuanyu Li; Juan Wang; Moutong Chen; Liang Xue; Yu Ding; et al. (International Journal of Food Microbiology, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Phosphorus mediated rhizosphere mobilization and apoplast precipitation regulate rare earth element accumulation in Phytolacca americana - Chong Liu; Ting-Xuan Ding; Wen-Shen Liu; Ye-Tao Tang; Rong-Liang Qiu (Plant and Soil, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Spatial distributions of intra-community tree species under topographically variable conditions - Ting Lv; Rong Zhao; Ning-jie Wang; Lei Xie; Yue-yao Feng; Yao Li; Hui Ding; Yan-ming Fang (Journal of Mountain Science, 2023)

Low-dose tributyltin triggers human chondrocyte senescence and mouse articular cartilage aging - Yao-Pang Chung; Te-I Weng; Ding-Cheng Chan; Rong-Sen Yang; Shing-Hwa Liu (Archives of Toxicology, 2023)

Disinfection by-products as environmental contaminants of emerging concern: a review on their occurrence, fate and removal in the urban water cycle - Rong Xiao; Tian Ou; Shunke Ding; Chao Fang; Zuxin Xu; Wenhai Chu (Critical Reviews in Environmental Science and Technology, 2023)

Life cycle assessment-driven collaborative optimization model of power dry cutting for face-hobbing hypoid gear production - Han Ding; Shifeng Rong; Kaibin Rong; Jinyuan Tang; Zhenyu Zhou; Jiange Zhang; Guowen Li (Journal of Cleaner Production, 2023)

Enhanced breakdown strength and electrostatic energy density of polymer nanocomposite films realized by heterostructure ZnO-ZnS nanoparticles - Jie Liu; Linye Ji; Junyi Yu; Shanjun Ding; Suibin Luo; Baojin Chu; Jianbin Xu; Rong Sun; Shuhui Yu (Chemical Engineering Journal, 2023)

Poly(ionic liquid) boosts overall performance of electrocatalytic reduction of low concentration of CO gas - Guo-Yi Duan; Xiao-Qiang Li; Jun-Wu Chen; Guang-Rong Ding; Peng-Xin Guan; Bao-Hua Xu (Chemical Engineering Journal, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Improved lithium-ion batteries with coral-like anodes made of recycled spherical porous silicon coated with nitrogen-doped carbon - Zhao Zhang; Fengshuo Xi; Xiuhua Chen; Shaoyuan Li; Wenhui Ma; Zhao Ding; Tao Qu; Yongnian Dai; Rong Deng (Environmental Chemistry Letters, 2022)

Plasma Exo-miRNAs Correlated with AD-Related Factors of Chinese Individuals Involved in Aβ Accumulation and Cognition Decline - Lifang Wang; Hefu Zhen; Yuzhe Sun; Shuang Rong; Benchao Li; Zhijie Song; Zhili Liu; Zhiming Li; Jiahong Ding; Huanming Yang; Xiuqing Zhang; Haixi Sun; et al. (Molecular Neurobiology, 2022)
Numerous studies have investigated the risk factors of Alzheimer’s disease (AD); however, AD-risk factors related miRNAs were rarely reported. In this study, AD-risk factor related miRNAs of 105 Chinese individuals (45 AD patients and 60 cognitively normal controls) were investigated. The results showed that Hsa-miR-185-5p, Hsa-miR-20a-5p, and Hsa-miR-497-5p were related to AD and education, Hsa-miR-185-5p, Hsa-miR-181c-5p, Hsa-miR-664a-3p, Hsa-miR-27a-3p, Hsa-miR-451a, and Hsa-miR-320a were related to AD and depression. Target prediction of above miRNAs showed that these miRNAs were involved in the generation and clearance of amyloid-beta (Aβ), important molecules related to cognition, and disease-activated microglia response to AD. It is worth noting that Hsa-miR-185-5p was related to both education and depression, whose decreased expression pattern in AD patients was alleviated by education and enhanced by depression, and participates in Aβ generation and accumulation. Our results indicated that certain education and depression factors can contribute to AD progression by modulating miRNA expression, implying that preventive interventions might alter AD progression in Chinese patients.

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

Does the construction of ecological civilization institution system promote the green innovation of enterprises? A quasi-natural experiment based on China’s national ecological civilization pilot zones - Jundong Hou; Rong Zhou; Fei Ding; Haixiang Guo (Environmental Science and Pollution Research, 2022)

SWI2/SNF2 chromatin remodeling ATPases SPLAYED and BRAHMA control embryo development in rice - Qian Xun; Min Mei; Ye Song; Chenyu Rong; Jiajun Liu; Tianhui Zhong; Yanfeng Ding; Chengqiang Ding (Plant Cell Reports, 2022)

Neiella holothuriorum sp. nov., isolated from the gut of a sea cucumber Apostichopus japonicus - Xin-Feng Bai; Xue-Lian Lv; Xue Liu; Ting-Ting Cui; Mian-Song Zhang; Ning Ding; Chang-Heng Liu; Ai-Rong Jia (Antonie van Leeuwenhoek, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Transgelin-2 interacts with CD44 to regulate Notch1 signaling pathway and participates in colorectal cancer proliferation and migration - Rong Ding; Guoyu Li; Yueyi Yao; Lijuan Zhang; Xuan Zhang; Jiayi Li; Tao Shen; Yi Gao; Tao Wu; Shuzhen Kong; Ming Huang; Yunfeng Li (Journal of Physiology and Biochemistry, 2022)

The anticancer potential of the dietary polyphenol rutin: Current status, challenges, and perspectives - Arakkaveettil Kabeer Farha; Ren-You Gan; Hua-Bin Li; Ding-Tao Wu; Atanas G. Atanasov; Khalid Gul; Jia-Rong Zhang; Qiong-Qiong Yang; Harold Corke (Critical Reviews in Food Science and Nutrition, 2022)

Promotional effect of ZrO2 and WO3 on bimetallic Pt-Pd diesel oxidation catalyst - Rongrong Fan; Zhaoqiang Li; Yu Wang; Yan Wang; Zhiyong Ding; Cheng Zhang; Na Kang; Xin Guo; Rong Wang (Environmental Science and Pollution Research, 2022)

Evolution of pore structure in organic shale with type III kerogen and high kaolinite content in Ningwu Basin - Qiang Xu; Hangbing Lin; Yue Zhao; Bo Wang; Bin Ma; Rong Ding; Jianxin Wang; Tao Hou (Frontiers of Earth Science, 2021)

Immune responses and protective efficacy of outer membrane protein ExbB of Pseudomonas fluorescens against Aeromonas hydrophila and Pseudomonas fluorescens affecting Carassius auratus - Wei Sun; Na Rong; Sijie Jian; Chao Kang; Chunlin Chen; Rui Chen; Rui Ding; Chen Chen; Xiang Liu (Aquaculture International, 2021)

Phenolic glycosides and flavonoids with antioxidant and anticancer activities from Desmodium caudatum - Qian-Nan Xu; Dan Zhu; Guang-Hui Wang; Ting Lin; Cui-Ling Sun; Rong Ding; Wen-Jing Tian; Hai-Feng Chen (Natural Product Research, 2021)

Mixing overstory tree- and understory fern-derived dissolved organic carbon produces non-additive effects on biodegradation in subtropical forests of southern China - Su-Li Li; Zhi Zheng; Yi-Dong Ding; Jia-Wen Xu; Rong Mao (Plant and Soil, 2021)

Tree mycorrhizal effect on litter-leached DOC amounts and biodegradation is highly dependent on leaf habits in subtropical forests of southern China - Yi-Dong Ding; Xin-Yi Xie; Jing-Hao Ji; Qian-Qian Li; Jia-Wen Xu; Rong Mao (Journal of Soils and Sediments, 2021)

Pepsinogen C expression–related lncRNA/circRNA/mRNA profile and its co-mediated ceRNA network in gastric cancer - Li-rong Yan; Han-xi Ding; Shi-xuan Shen; Xiao-dong Lu; Yuan Yuan; Qian Xu (Functional & Integrative Genomics, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Source–sink dynamics assists the maintenance of a pollinating wasp - Xin Tong; Yuan‐Yuan Ding; Jun‐Yin Deng; Rong Wang; Xiao‐Yong Chen (Molecular Ecology, 2021)
Dispersal that unites spatially subdivided populations into a metapopulation with source–sink dynamics is crucial for species persistence in fragmented landscapes. Understanding such dynamics for pollinators is particularly urgent owing to the ongoing global pollination crisis. Here, we investigated the population structure and source–sink dynamics of a pollinating wasp ( Wiebesia sp. 3) of Ficus pumila in the Zhoushan Archipelago of China. We found significant asymmetry in the pairwise migrant numbers for 22 of 28 cases on the historical timescale, but only two on the contemporary timescale. Despite a small population size, the sole island not colonized by a superior competitor wasp ( Wiebesia sp. 1) consistently behaved as a net exporter of migrants, supplying large sinks. Comparable levels of genetic diversity, with few private alleles and low genetic differentiation (total F st : 0.03; pairwise F st : 0.0005–0.0791), were revealed among all the islands. There was a significant isolation‐by‐distance pattern caused mainly by migration between the competition‐free island and other islands, otherwise the pattern was negligible. The clustering analysis failed to detect multiple gene pools for the whole region. Thus, the sinks were most probably organized into a patchy population. Moreover, the estimates of effective population sizes were comparable between the two timescales. Thus the source–sink dynamics embedded within a well‐connected population network may allow Wiebesia sp. 3 to persist at a competitive disadvantage. This study provides evidence that metapopulations in the real world may be complicated and changeable over time, highlighting the necessity to study such metapopulations in detail.

Reduction of mussel metamorphosis by inactivation of the bacterial thioesterase gene via alteration of the fatty acid composition - Xiao-Meng Hu; Junbo Zhang; Wen-Yang Ding; Xiao Liang; Rong Wan; Sergey Dobretsov; Jin-Long Yang (Biofouling, 2021)

Dual effects of insect fecundity overdispersion on the Wolbachia establishment and the implications for epidemic biocontrol - Xin Tong; Stephen G. Compton; Jing Jiao; Yan Chen; Yuan-Yuan Ding; Rong Wang; Xiao-Yong Chen (Journal of Pest Science, 2021)

Removal of phosphorus and ammonium from municipal wastewater treatment plant effluent by manganese ore in a simulated constructed wetland - Yungui Li; Xueying Bai; Ruonan Ding; Wenxuan Lv; Ying Long; Liang Wei; Fachun Xiang; Rong Wang (Environmental Science and Pollution Research, 2021)

Microvesicles derived from human umbilical cord mesenchyme promote M2 macrophage polarization and ameliorate renal fibrosis following partial nephrectomy via hepatocyte growth factor - Tao Du; Guanqun Ju; Jun Zhou; Liang Zhong; Lu Rong; Wenxia Chen; Xiaoli Zhang; Ruijin Zhou; Degang Ding; Tongyu Ji (Human Cell, 2021)

Bi-allelic BRWD1 variants cause male infertility with asthenoteratozoospermia and likely primary ciliary dyskinesia - Ting Guo; Chao-Feng Tu; Dan-Hui Yang; Shui-Zi Ding; Cheng Lei; Rong-Chun Wang; Lv Liu; Xi Kang; Xiao-Qing Shen; Yi-Feng Yang; Zhi-Ping Tan; Yue-Qiu Tan; et al. (Human Genetics, 2021)

Isolation and Identification of Pseudomonas sp. Strain DY-1 from Agricultural Soil and Its Degradation Effect on Prometryne - Dong Liang; Ming-yue Ding; Chang-yixin Xiao; Ya-wen Shen; Yin-yue Wang; Hai-tao Li; Rong-mei Liu; Ji-guo Gao (Current Microbiology, 2021)

Complete nucleotide sequence of a new carlavirus infecting Aconitum carmichaelii in China - Rong Wang; Bingwei Chen; Yong Li; Mengji Cao; Wanlong Ding (Archives of Virology, 2021)

Regenerable, anti-biofouling covalent organic frameworks for monitoring and extraction of uranium from seawater - Yi-Di Wu; Wei-Rong Cui; Cheng-Rong Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Chemistry Letters, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Controlled-release N fertilizer to mitigate ammonia volatilization from double-cropping rice - Chang Tian; Xuan Zhou; Zheli Ding; Qiang Liu; Guixian Xie; Jianwei Peng; Xiangming Rong; Yuping Zhang; Yong Yang; Mamdouh A. Eissa (Nutrient Cycling in Agroecosystems, 2021)
Controlled-release nitrogen fertilizer (CRNF) can effectively enhance crop yields and raise the efficiency of nitrogen fertilizer in agroecosystems. In the present study, the volatilization of NH 3 was determined by airflow enclosure chamber technique after the application of different CRNF rates in double-cropping rice fields in southern China for continuous 3 years. The early and late season rice (ESR and LSR) were cultivated each year. The results showed that the total NH 3 volatilization losses ranged from 25 to 56 kg N ha −1 in ESR and from 32 to 61 kg N ha −1 in LSR. The loss of N to the total applied N ranged from 12 to 29% in ESR and from 12 to 27% in LSR. The application of CRNF significantly reduced the cumulative NH 3 volatilization losses by 20–43% for ESR and by 20–32% for LSR compared with conventional urea application. CRNF in LSR was less effective to reduce NH 3 volatilization than that in ESR. Furthermore, the application of 80% of N rate in the form of CRNF gave higher grain yield and apparent nitrogen recovery efficiency (ANRE) than that of application of 100% of N rate from conventional urea. CRNF can effectively reduce NH 3 volatilization, and increase rice yield and ANRE. Considering higher price of CRNF, the application of CRNF at lower (20% applied N) rate than conventional urea in LSR may be a reasonable fertilization strategy for improving N use efficiency, environment effectiveness, and sustaining the development of rice production systems in double-cropping rice.

A new phenolic glycoside from Trollius chinensis Bunge with anti-inflammatory and antibacterial activities - Jie Feng; Danyang Zhao; Qiannan Xu; Xiangzhong Liu; Mi Zhou; Xiansheng Ye; Ting Lin; Guanghui Wang; Cuiling Sun; Rong Ding; Wenjing Tian; Haifeng Chen (Natural Product Research, 2020)

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

A new oleanane type pentacyclic triterpenoid saponin from the husks of xanthoceras sorbifolium bunge and its neuroprotection on PC12 cells injury induced by Aβ 25-35 - Kewen Ding; Sirui Guo; Weiwei Rong; Qing Li; Ran Liu; Huarong Xu; Yidi Yin; Kaishun Bi (Natural Product Research, 2020)

GaHD1, a candidate gene for the Gossypium arboreum SMA-4 mutant, promotes trichome and fiber initiation by cellular H2O2 and Ca2+ signals - Mingquan Ding; Yuefen Cao; Shae He; Jian Sun; Huaqin Dai; Hua Zhang; Chendong Sun; Yurong Jiang; Andrew H. Paterson; Junkang Rong (Plant Molecular Biology, 2020)

How does experience impact the adoption willingness of battery electric vehicles? The role of psychological factors - Rong Liu; Zhihua Ding; Xin Jiang; Jing Sun; Yanling Jiang; Wei Qiang (Environmental Science and Pollution Research, 2020)

MiR-146a-5p promotes IL-1β-induced chondrocyte apoptosis through the TRAF6-mediated NF-kB pathway - Jiahua Shao; Zheru Ding; Jinhui Peng; Rong Zhou; Lexiang Li; Qirong Qian; Yi Chen (Inflammation Research, 2020)

Central autonomic network functional connectivity: correlation with baroreflex function and cardiovascular variability in older adults - Kan Ding; Takashi Tarumi; Ciwen Wang; Steven Vernino; Rong Zhang; David C. Zhu (Brain Structure and Function, 2020)

Disruption of functional connectivity among subcortical arousal system and cortical networks in temporal lobe epilepsy - Rong Li; Chongyu Hu; Liangcheng Wang; Ding Liu; Dingyang Liu; Wei Liao; Bo Xiao; Huafu Chen; Li Feng (Brain Imaging and Behavior, 2020)

Interaction between Translocation-associated membrane protein 1 and σC protein of novel duck reovirus controls virus infectivity - Rong Xiao; Xiaoyun Mi; Jiahui Sun; Mingyang Ding; Chuanfeng Li; Jie Zhu; Guangqing Liu; Wenge Ma; Hailong Zhou; Zongyan Chen (Virus Genes, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

First report of cucumber mosaic virus infecting bahizi (Angelica dahurica) in China - Ruo-Fan Wei; Wan-Long Ding; Yong Li; Rong Wang (Journal of Plant Pathology, 2020)

Reference Point Based Multi-Objective Optimization of Reservoir Operation: a Comparison of Three Algorithms - Rong Tang; Ke Li; Wei Ding; Yuntao Wang; Huicheng Zhou; Guangtao Fu (Water Resources Management, 2020)

Complete genomic sequence of crow-dipper mosaic-associated virus, a novel macluravirus infecting Pinellia ternata - Rong Wang; Bingwei Chen; Yong Li; Tianyou Wang; Wanlong Ding (Archives of Virology, 2020)

Preferential insertion of a Ty1 LTR-retrotransposon into the A sub-genome’s HD1 gene significantly correlated with the reduction in stem trichomes of tetraploid cotton - Mengling Tang; Xingcheng Wu; Yuefen Cao; Yuan Qin; Mingquan Ding; Yurong Jiang; Chengdong Sun; Hua Zhang; Andrew H. Paterson; Junkang Rong (Molecular Genetics and Genomics, 2020)

Effects of topography on dynamic responses of single piles under vertical cyclic loading - Li-ming Qu; Xuan-ming Ding; Chong-rong Wu; Yong-hong Long; Jin-chuan Yang (Journal of Mountain Science, 2020)

Cell bioreactor culture of Orostachys cartilaginous A. Bor. and involvement of nitric oxide in methyl jasmonate-induced flavonoid synthesis - Yue-Jun Hao; Xi-Hua Cui; Jin-Rong Li; Xiao-Li An; Hao-Ding Sun; Xuan-Chun Piao; Mei-Lan Lian (Acta Physiologiae Plantarum, 2020)

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Development, Optimization, and Evaluation In Vitro/In Vivo of Oral Liquid System for Synchronized Sustained Release of Levodopa/Benserazide - Yang Qu; Wen-Long Lai; Yuan-Rong Xin; Fei-Qin Zhu; Yuan Zhu; Li Wang; Yue-ping Ding; Ying Xu; Hong-Fei Liu (AAPS PharmSciTech, 2019)

Tradeoff Analysis Index for Many-Objective Reservoir Optimization - Rong Tang; Wei Ding; Lei Ye; Yuntao Wang; Huicheng Zhou (Water Resources Management, 2019)

Interseismic Coupling in the Central Nepalese Himalaya: Spatial Correlation with the 2015 Mw 7.9 Gorkha Earthquake - Shuiping Li; Qi Wang; Gang Chen; Ping He; Kaihua Ding; Yunguo Chen; Rong Zou (Pure and Applied Geophysics, 2019)

Trends of sea surface wind energy over the South China Sea - Bo Jiang; Yongliang Wei; Jie Ding; Rong Zhang; Yuxin Liu; Xiaoyong Wang; Yizhou Fang (Journal of Oceanology and Limnology, 2019)

Identification and mapping of a photoperiod response gene (QPpd.zafu-4A) on wild emmer wheat (Triticum turgidum L.) chromosome 4AL - Jinsheng Yu; Yunzheng Miao; Siqing Yang; Zhaobin Shi; Nana Miao; Mingquan Ding; Hua Zhang; Yurong Jiang; Junkang Rong (Euphytica, 2019)

Enhancing the mechanical properties of marine clay using cement solidification - Bhim Kumar Dahal; Jun-Jie Zheng; Rong-Jun Zhang; Ding-Bao Song (Marine Georesources & Geotechnology, 2019)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

Presurgical localization and spatial shift of resting state networks in patients with brain metastases - Ju-Rong Ding; Fangmei Zhu; Bo Hua; Xingzhong Xiong; Yuqiao Wen; Zhongxiang Ding; Paul M. Thompson (Brain Imaging and Behavior, 2019)

A new benzofuran from the heartwood of Dalbergia latifolia - Rong-Hua Liu; Dan-Yi Mei; Shuai Lin; Ding-Qing Wang; Feng Shao; Lan-Ying Chen; Shan-Liang Guo (Natural Product Research, 2019)

Can Chinese residential low-carbon consumption behavior intention be better explained? The role of cultural values - Xin Jiang; Zhihua Ding; Rong Liu (Natural Hazards, 2019)

A frameshift mutation in exon 19 of MLH1 in a Chinese Lynch syndrome family: a pedigree study - Qiao-qi Sui; Wu Jiang; Xiao-dan Wu; Yi-hong Ling; Zhi-zhong Pan; Pei-rong Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Arctic Climate Changes Based on Historical Simulations (1900‒2013) with the CAMS-CSM - Ting Wei; Jian Li; Xinyao Rong; Wenjie Dong; Bingyi Wu; Minghu Ding (Journal of Meteorological Research, 2018)

Evaluating tacrolimus pharmacokinetic models in adult renal transplant recipients with different CYP3A5 genotypes - Can Hu; Wen-jun Yin; Dai-yang Li; Jun-jie Ding; Ling-yun Zhou; Jiang-lin Wang; Rong-rong Ma; Kun Liu; Ge Zhou; Xiao-cong Zuo (European Journal of Clinical Pharmacology, 2018)

Mid–Late Cretaceous igneous activity in South China: the Qianjia example, Hainan Island - Sai-Jun Sun; Li-Peng Zhang; Rong-Qing Zhang; Xing Ding; Hong-Li Zhu; Zhao-Feng Zhang; Wei-Dong Sun (International Geology Review, 2018)

First report of tomato yellow Leaf curl virus and cucumber mosaic virus infecting Huoxiang (Agastache rugosa) in CHINA - Rong Wang; Yong Li; Jia-Li Dong; Wan-Long Ding (Journal of Plant Pathology, 2018)

Altered connectivity patterns among resting state networks in patients with ischemic white matter lesions - Ju-Rong Ding; Xin Ding; Bo Hua; Xingzhong Xiong; Yuqiao Wen; Zhongxiang Ding; Qingsong Wang; Paul Thompson (Brain Imaging and Behavior, 2018)

Seasonal Variation and Exposure Risks of Perchlorate in Soil, Indoor Dust, and Outdoor Dust in China - Yiwen Li; Ruoying Liao; Zhiwei Gan; Bing Qu; Rong Wang; Mengqin Chen; Sanglan Ding; Shijun Su (Archives of Environmental Contamination and Toxicology, 2018)

Complete nucleotide sequence of a new carlavirus in chrysanthemums in China - Rong Wang; Jiali Dong; Zhen Wang; Tao Zhou; Yong Li; Wanlong Ding (Archives of Virology, 2018)

Sucrose is involved in the regulation of iron deficiency responses in rice (Oryza sativa L.) - Peng-Fei Chen; Lin Chen; Zheng-Rong Jiang; Gao-Peng Wang; Shao-Hua Wang; Yan-Feng Ding (Plant Cell Reports, 2018)

Effects of diurnal temperature range on mortality in Hefei city, China - Jing Tang; Chang-chun Xiao; Yu-rong Li; Jun-qing Zhang; Hao-yuan Zhai; Xi-ya Geng; Rui Ding; Jin-xia Zhai (International Journal of Biometeorology, 2018)

Investigation of the Mechanism of Roof Caving in the Jinchuan Nickel Mine, China - Kuo Ding; Fengshan Ma; Jie Guo; Haijun Zhao; Rong Lu; Feng Liu (Rock Mechanics and Rock Engineering, 2018)

Detrital apatite fission track constraints on Cenozoic tectonic evolution of the northeastern Qinghai-Tibet Plateau, China: Evidence from Cenozoic strata in Lulehe section, Northern Qaidam Basin - Ding-ding Du; Cheng-jun Zhang; Muhammad Saleem Mughal; Xiao-yu Wang; Dembele Blaise; Jun-ping Gao; Yuan Ma; Xin-rong Luo (Journal of Mountain Science, 2018)

A new diaryl 1, 2-diketone from the heartwood of Dalbergia latifolia - Rong-hua Liu; Ding-qing Wang; Pu-zhao Zhang; Feng Shao; Lan-ying Chen; Hui-lian Huang; Shuai Lin (Natural Product Research, 2018)

Concentrations and Exposure Evaluation of Metals in Diverse Food Items from Chengdu, China - Rong Wang; Bifeng Zhong; Lu Pi; Fuyu Xie; Mengqin Chen; Sanglan Ding; Shijun Su; Zhi Li; Zhiwei Gan (Archives of Environmental Contamination and Toxicology, 2018)

Phytoactinopolyspora halotolerans sp. nov., a halotolerant actinobacterium isolated from a saline soil in Xinjiang, northwest of China - Yang Ji; Wei-Xun Chunyu; En-Yuan Li; Zhang-Gui Ding; Min Yin; Yu-Rong Zhao; Yun Wang; Shu-Kun Tang (Antonie van Leeuwenhoek, 2018)

ALDH2 genes are negatively correlated with natural deastringency in Chinese PCNA persimmon (Diospyros kaki Thunb.) - Jun-Chi Xu; Jin-Ge Ding; Jian-Ping Gan; Rong-Li Mo; Li-Qing Xu; Qing-Lin Zhang; Zheng-Rong Luo (Tree Genetics & Genomes, 2017)

Targeted Metagenome Based Analyses Show Gut Microbial Diversity of Inflammatory Bowel Disease patients - Zhibing Qiu; Haijing Yang; Lan Rong; Weiqun Ding; Jiazhen Chen; Liang Zhong (Indian Journal of Microbiology, 2017)

Seasonal variations of organic carbon and nitrogen in the upper basins of Yangtze and Yellow Rivers - Xiang-ying Li; Yong-jian Ding; Tian-ding Han; Jian-zhong Xu; Shi-chang Kang; Qing-bai Wu; Mika Sillanpää; Zhong-bo Yu; Cong-rong Yu (Journal of Mountain Science, 2017)

A new pyridine alkaloid from Zingiberis rhizoma - Feng Shao; Ding-qing Wang; Wei Xiong; Pu-zhao Zhang; Guang-qiang Ma; Rong-hua Liu; Xue-lian Yao (Natural Product Research, 2017)

Benzimidazole derivative M084 extends the lifespan of Caenorhabditis elegans in a DAF-16/FOXO-dependent way - Ai-Jun Ding; Gui-Sheng Wu; Bin Tang; Xuechuan Hong; Michael X. Zhu; Huai-Rong Luo (Molecular and Cellular Biochemistry, 2017)

Oral administration of Schisandra chinensis extract suppresses Dnmt1 expression in Kunming mice ovaries - Feng-Rui Wu; Deng-kun Li; Mi-mi Su; Yong Liu; Biao Ding; Rong Wang; Wen-yong Li (Genes & Genomics, 2016)

The LXR ligand GW3965 inhibits Newcastle disease virus infection by affecting cholesterol homeostasis - Xiang-xiang Sheng; Ying-jie Sun; Yuan Zhan; Yu-rong Qu; Hua-xia Wang; Miao Luo; Ying Liao; Xu-sheng Qiu; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2016)

Experimental research on seismoelectric effects in sandstone - Rong Peng; Jian-Xing Wei; Bang-Rang Di; Pin-Bo Ding; Zi-Chun Liu (Applied Geophysics, 2016)

Impact of extreme oxygen consumption by pollutants on macroinvertebrate assemblages in plain rivers of the Ziya River Basin, north China - Yuekui Ding; Nan Rong; Baoqing Shan (Environmental Science and Pollution Research, 2016)

To perceive a perfect Dora Maar in peripheral vision - Rong-Ding He; Tao Su; Yang Yang; Ying Liu; Yan Wei; Rong-Qiao He (Science China Life Sciences, 2016)

Chromosome elimination of hexaploid common wheat mediated by interaction between Chinese Spring cytoplasm and a genetic factor(s) on chromosome arm 1BL of wild emmer - Y. R. Jiang; M. D. He; M. Q. Ding; J. K. Rong (Euphytica, 2016)

The strong El Niño of 2015/16 and its dominant impacts on global and China's climate - Panmao Zhai; Rong Yu; Yanjun Guo; Qingxiang Li; Xuejuan Ren; Yaqiang Wang; Wenhui Xu; Yanju Liu; Yihui Ding (Journal of Meteorological Research, 2016)

Increasing the immune activity of exosomes: the effect of miRNA-depleted exosome proteins on activating dendritic cell/cytokine-induced killer cells against pancreatic cancer - Ri-sheng Que; Cheng Lin; Guo-ping Ding; Zheng-rong Wu; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

Improving the antioxidant activity and enriching salvianolic acids by the fermentation of Salvia miltiorrhizae with Geomyces luteus - Yun Xing; Le Cai; Tian-peng Yin; Yang Chen; Jing Yu; Ya-rong Wang; Zhong-tao Ding (Journal of Zhejiang University-SCIENCE B, 2016)

Composition of phosphorus in wetland soils determined by SMT and solution 31P-NMR analyses - Wenqiang Zhang; Xin Jin; Yuekui Ding; Xiaolei Zhu; Nan Rong; Jie Li; Baoqing Shan (Environmental Science and Pollution Research, 2016)

A highly efficient grapevine mesophyll protoplast system for transient gene expression and the study of disease resistance proteins - Feng-Li Zhao; Ya-Juan Li; Yang Hu; Yu-Rong Gao; Xue-Wen Zang; Qin Ding; Yue-Jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Phosphorus speciation of sediments from lakes of different tropic status in Eastern China - Wenqiang Zhang; Nan Rong; Xin Jin; Jie Li; Yuekui Ding; Xiaolei Zhu; Baoqing Shan (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Genetic fine mapping and candidate gene analysis of the Gossypium hirsutum Ligon lintless-1 (Li1) mutant on chromosome 22(D) - Yurong Jiang; Mingquan Ding; Yuefen Cao; Fen Yang; Hua Zhang; Shae He; Huaqin Dai; Huanfeng Hao; Junkang Rong (Molecular Genetics and Genomics, 2015)

Heavy metals in wild marine fish from South China Sea: levels, tissue- and species-specific accumulation and potential risk to humans - Jin-Ling Liu; Xiang-Rong Xu; Zhen-Hua Ding; Jia-Xi Peng; Ming-Hua Jin; You-Shao Wang; Yi-Guo Hong; Wei-Zhong Yue (Ecotoxicology, 2015)

Purification and Antioxidant Property of Antioxidative Oligopeptide from Short-Necked Clam ( Ruditapes philippinarum ) Hydrolysate In Vitro - Rong Li; Zui-su Yang; Yu Sun; Li Li; Jia-Bin Wang; Guofang Ding (Journal of Aquatic Food Product Technology, 2015)

Analysis of methylation-sensitive amplified polymorphism in different cotton accessions under salt stress based on capillary electrophoresis - Baohua Wang; Rong Fu; Mi Zhang; Zhenqian Ding; Lei Chang; Xinyu Zhu; Yafeng Wang; Baoxiang Fan; Wuwei Ye; Youlu Yuan (Genes & Genomics, 2015)

Multiple Mesozoic magma processes formed the 240–185 Ma composite Weishan pluton, South China: evidence from geochronology, geochemistry, and Sr-Nd isotopes - Xing Ding; Wei-Dong Sun; Wei-Feng Chen; Pei-Rong Chen; Tao Sun; Sai-Jun Sun; Chiou-Ting Lin; Fu-Kun Chen (International Geology Review, 2015)

Molecular characterization of a transcriptionally active Ty1/copia-like retrotransposon in Gossypium - Yuefen Cao; Yurong Jiang; Mingquan Ding; Shae He; Hua Zhang; Lifeng Lin; Junkang Rong (Plant Cell Reports, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Optimized Preparation of a 99mTc-Radiolabeled Probe for Tracing MicroRNA - Lei Kang; Xiao-jie Xu; Chao Ma; Rong-fu Wang; Ping Yan; Chun-li Zhang; Hong-wei Sun; Ding Li (Cell Biochemistry and Biophysics, 2015)

Genome-wide investigation and transcriptome analysis of the WRKY gene family in Gossypium - Mingquan Ding; Jiadong Chen; Yurong Jiang; Lifeng Lin; YueFen Cao; Minhua Wang; Yuting Zhang; Junkang Rong; Wuwei Ye (Molecular Genetics and Genomics, 2015)

Biological Roles of Olfactory Ensheathing Cells in Facilitating Neural Regeneration: A Systematic Review - Hao Yang; Bao-Rong He; Ding-Jun Hao (Molecular Neurobiology, 2015)

Fibroblast Growth Factor 4 Is Required but not Sufficient for the Astrocyte Dedifferentiation - Guo-Dong Feng; Bao-Rong He; Fan Lu; Lin-Hong Liu; Lingling Zhang; Bo Chen; Zu-Ping He; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Three dimensional reconstruction of bone-cartilage transitional structures based on semi-automatic registration and automatic segmentation of serial sections - Hua Guo; Zheng-Wei Xu; Bao-Rong He; Ding-Jun Hao; Wei-Guo Bian (Tissue Engineering and Regenerative Medicine, 2014)

Effects of Estradiol on Voltage-Gated Potassium Channels in Mouse Dorsal Root Ganglion Neurons - Juan Du; Qiang Wang; Fang Hu; Jun Wang; Haixia Ding; Rong Gao; Hang Xiao; Lin Wang (The Journal of Membrane Biology, 2014)

Co-delivery of Dexamethasone and Green Tea Polyphenols Using Electrospun Ultrafine Fibers for Effective Treatment of Keloid - Jinrong Li; Rong Fu; Long Li; Guang Yang; Shan Ding; Zhendong Zhong; Shaobing Zhou (Pharmaceutical Research, 2014)

Effect of NeuroD Gene Silencing on the Migration and Invasion of Human Pancreatic Cancer Cells PANC-1 - Yang Wang; Dong Wei Su; Li Gao; Gui Ling Ding; Can Rong Ni; Ming Hua Zhu (Cell Biochemistry and Biophysics, 2014)

Phagocytic Removal of Neuronal Debris by Olfactory Ensheathing Cells Enhances Neuronal Survival and Neurite Outgrowth via p38MAPK Activity - Bao-Rong He; Song-Tao Xie; Ming-Mei Wu; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Clodronate-superparamagnetic iron oxide-containing liposomes attenuate renal injury in rats with severe acute pancreatitis - Sheng-chun Dang; Yan-hua Zeng; Ping-jiang Wang; Bao-ding Chen; Rong-fang Chen; Arun Kumar Singh; Pankaj Kumar; Shu Feng; Lei Cui; Hao Wang; Jian-xin Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Manganese concentrations in maternal–infant blood and birth weight - Limei Chen; Guodong Ding; Yu Gao; Pei Wang; Rong Shi; Hong Huang; Ying Tian (Environmental Science and Pollution Research, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Estrogen receptor α gene PvuII polymorphism and coronary artery disease: a meta-analysis of 21 studies - Jie Ding; Hui Xu; Xiang Yin; Fu-rong Zhang; Xiao-ping Pan; Yi-an Gu; Jun-zhu Chen; Xiao-gang Guo (Journal of Zhejiang University-SCIENCE B, 2014)

Characterization of eubacterial and archaeal community diversity in the pit mud of Chinese Luzhou-flavor liquor by nested PCR–DGGE - Xiao-Fei Ding; Chong-De Wu; Li-Qiang Zhang; Jia Zheng; Rong-Qing Zhou (World Journal of Microbiology and Biotechnology, 2014)

A Highly Selective Turn-On Fluorescent Chemosensor for Zinc Ion in Aqueous Media - Zeng-chen Liu; Zheng-yin Yang; Yan-xia Li; Bao-dui Wang; Yong Li; Tian-rong Li; Yong-jie Ding (Journal of Fluorescence, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Effects of High Zinc Levels on the Lipid Synthesis in Rat Hepatocytes - Xinwei Li; Yuan Guan; Xiaoxia Shi; Hongyan Ding; Yuxiang Song; Chenggang Li; Rong Liu; Guowen Liu (Biological Trace Element Research, 2013)

Potential hepatotoxicity of geniposide, the major iridoid glycoside in dried ripe fruits of Gardenia jasminoides (Zhi-zi) - Yue Ding; Tong Zhang; Jian-sheng Tao; Li-ying Zhang; Jian-rong Shi; Guang Ji (Natural Product Research, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Effect of maternal age on the outcomes of in vitro fertilization and embryo transfer (IVF-ET) - JunHao Yan; KeLiang Wu; Rong Tang; LingLing Ding; Zi-Jiang Chen (Science China Life Sciences, 2012)

Cloning and characterization of miRNAs from maize seedling roots under low phosphorus stress - Zhiming Zhang; Haijian Lin; Yaou Shen; Jian Gao; Kui Xiang; Li Liu; Haiping Ding; Guangsheng Yuan; Hai Lan; Shufeng Zhou; Maojun Zhao; Shibin Gao; et al. (Molecular Biology Reports, 2012)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

High mobility group box-1 induces migration of vascular smooth muscle cells via TLR4-dependent PI3K/Akt pathway activation - Jian Yang; Lihua Chen; Jun Yang; Jiawang Ding; Han Rong; Wusong Dong; Xinxin Li (Molecular Biology Reports, 2012)

Glypican-3, a novel prognostic marker of hepatocellular cancer, is related with postoperative metastasis and recurrence in hepatocellular cancer patients - Su Ning; Chen Bin; Huang Na; Shen Peng; Ding Yi; Ye Xiang-hua; Zeng Fang-yin; Zheng Da-yong; Luo Rong-cheng (Molecular Biology Reports, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Enhanced Biotransformation of 2-Phenylethanol with Ethanol Oxidation in a Solid–Liquid Two-Phase System by Active Dry Yeast - Shaofeng Rong; Baomei Ding; Xiaoli Zhang; Xuesong Zheng; Yifei Wang (Current Microbiology, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Theoretical investigation of the first-shell mechanism of acetylene hydration catalyzed by a biomimetic tungsten complex - Yan-Fang Liu; Rong-Zhen Liao; Wan-Jian Ding; Jian-Guo Yu; Ruo-Zhuang Liu (JBIC Journal of Biological Inorganic Chemistry, 2011)

Lingo2 variants associated with essential tremor and Parkinson’s disease - Yi-Wen Wu; K. M. Prakash; Tian-Yi Rong; Hui-Hua Li; Qin Xiao; Louis C. Tan; Wing-Lok Au; Jian-qing Ding; Sheng-di Chen; Eng-King Tan (Human Genetics, 2011)

QTL mapping for test weight by using F 2:3 population in maize - JUN-QIANG DING; JIN-LIANG MA; CHUN-RONG ZHANG; HUA-FANG DONG; ZHANG-YING XI; ZONG-LIANG XIA; JIAN-YU WU (Journal of Genetics, 2011)

Relaxation Effects of a Saturated Porous Media Using the Two-Dimensional Generalized Thermoelastic Theory - Gan-bin Liu; Shi-rong Ding; Rong-hua Ye; Xiao-hu Liu (Transport in Porous Media, 2011)

Validity and reliability testing of the Chinese (mainland) version of the 39-item Parkinson’s Disease Questionnaire (PDQ-39) - Wei Luo; Xiao-hong Gui; Bo Wang; Wen-ying Zhang; Zhi-yuan Ouyang; Yi Guo; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2010)

Immobilization of glucose oxidase on Fe3O4/SiO2 magnetic nanoparticles - Jun Huang; Rong Zhao; Hai Wang; Wenqi Zhao; Liyun Ding (Biotechnology Letters, 2010)

Expression of a bee venom phospholipase A2 from Apis cerana cerana in the baculovirus-insect cell - Li-rong Shen; Mei-hui Ding; Li-wen Zhang; Wei-guang Zhang; Liang Liu; Duo Li (Journal of Zhejiang University-SCIENCE B, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Potential role of the TLR4/IRAK-4 signaling pathway in the pathophysiology of acute pancreatitis in mice - Jun-Li Ding; Yuan Li; Xiang-Yu Zhou; Ling Wang; Bin Zhou; Rong Wang; Hong-Xiang Liu; Zong-Guang Zhou (Inflammation Research, 2009)

Reactions of 3-benzoyl-7-dimethylamino-4-hydroxycoumarin and their potential applications in solution- and solid-phase synthesis - Pei-Yu Kuo; Rong-Ren Chuang; Ding-Yah Yang (Molecular Diversity, 2009)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

An insulinoma with clinical and electroencephalographic features resembling complex partial seizures - Shuang Wang; Hai-tao Hu; Shu-qun Wen; Zhong-jin Wang; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2008)

Lance-adams syndrome: a report of two cases - Yan-xing Zhang; Jian-ren Liu; Biao Jiang; Hui-qin Liu; Mei-ping Ding; Shui-jiang Song; Bao-rong Zhang; Hong Zhang; Bin Xu; Huai-hong Chen; Zhong-jin Wang; Jian-zheng Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

A rapid and efficient DNA minipreparation suitable for screening transgenic plants - Rong-Cheng Lin; Zai-Song Ding; Liang-Bi Li; Ting-Yun Kuang (Plant Molecular Biology Reporter, 2001)

Beneficial effect of HCL-31D in murine models of endotoxaemia - Tz-Chong Chou; Chi-Yuan Li; Tzong-Ming Wu; Shang-Tao Tang; An-Rong Lee; Yu-An Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)